Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.

Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Metalloantitubercular compounds part 3: synthesis, crystal structure, spectroscopy, electrochemistry and antimycobacterial activity of the copper(II) ciproploxacin (cfH) complex and its phenanthroline adduct - Saha, D. K.; Patitungkho, S.; Padhye, S.; Deobagkar, D. N.; Ozarkar, A.; Bhadbhade, Mohan M.; Gonnade, Rajesh G. (Transition Metal Chemistry, 2005)
The X-ray crystal structures of two ciprofloxacin compounds, viz. [Cu(cfH)(2)(Cl)(2)] (.) 2MeOH (.) 6H2O (2) and [Cu(cfH)(phen)Cl]BF4 (.) 4H(2)O (3) are reported. Complex ( 2) has a distorted octahedral geometry, whereas for the nitrogen adduct (3) a distorted square-pyramidal geometry is seen. Significant enhancement in the antimycobacterial activity of the copper conjugates correlates with their copper redox couples (Cu2+/Cu+) probably due to its relevance to intracellular accumulations and subsequent role in generating oxidative stress.

New bis-andrographolide ether from androgphis paniculata nees and evaluation of anti-HIV activity - Reddy, V. L. N.; Reddy, S. M.; Ravikanth, V.; Krishnaiah, P.; Goud, T. V.; Rao, T. P.; Ram, T. S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Venkateswarlu, Y (Natural Product Research, 2005)
Novel bis-andrographolide ether (1) and six known compounds andrographolide, 14-deoxy-11,12-didehydroandrographolide, andrograpanin, 14-deoxyandrographolide, (+/-)-5- hydroxy-7,8-dimethoxyflavanone, and 5-hydroxy-7,8-dimethoxyflavone have been isolated from the aerial parts of Andrographis paniculota and their structures were established by spectral data. All the isolates were tested for the anti-HIV and cytotoxic activity.
Keywords: Acanthaceae; Andrographis paniculata; anti-HIV; bis-andrographolide ether; Cytotoxic activity

O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Self-assembly with degenerate prototropy - Baruah, Pranjal K.; Gonnade, Rajesh G.; Phalgune, U. D.; Sanjayan, G. J. (Journal of Organic Chemistry, 2005)
This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as ``single set of protameric pair (duplex)'' in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-1H-pyrimidine-4,6-diones, available in one step by the condensation of (x,a-dialkyl malonates and free guanidine, with isocyanates. Evidence from NMR spectroscopy, ESI mass spectrometry, and single-crystal X-ray diffraction studies confirmed the formation of molecular duplexes. The effect of electronic repulsion in duplex formation is also investigated. Their ready synthetic accessibility, remarkably high propensity to crystal formation, and the novel property of degenerate prototropy would make these novel self-assembling molecules promising candidates for many proposed applications.

Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Sulfonate protecting groups. synthesis of O- and C-methylated inositols: D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether - Sarmah, M. P.; Shashidhar, M. S.; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
Syntheses of D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether starting from myo-imositol are described. One or two of the inyo-inositol 1,3,5-orthoformate hydroxyl groups were protected as tosylates. These mono or ditosylates served as key intermediates for the preparation of O- and C-methyl inositols. Racemic 2,4-di-O-tosyl-myo-inositol 1,3,5-orthoformate was resolved as its diastereomeric camphanates. Use of sulfonate groups for the protection of inositol hydroxyl groups resulted in substantial improvement in the overall yield of O- and C-methyl inositols. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Orthoester; Protecting group; sulfonate

Hybrid foldamer with unique architecture from conformationally constrained aliphatic-aromatic amino acid conjugate - Srinivas, Deekonda; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Tetrahedron, 2006)
In this paper, we describe the design and synthesis of a novel hybrid foldamer, derived from a conformationally constrained aliphatic-aromatic amino acid conjugate that adopts a well-defined, compact, three-dimensional structure, governed by a combined conformational restriction imposed by the individual amino acids from which the foldamer is composed. Conformational investigations confirmed the prevalence of a unique doubly bent conformation for the foldamer, in both solid and solution states, as evidenced from single crystal X-ray and 2D NOESY studies, respectively. The findings suggest that constrained aliphatic-aromatic amino acid conjugates offer new avenues for the de novo design of hybrid foldamers with distinctive structural architectures. Furthermore, the de novo design strategy disclosed herein has the potential for significantly augmenting the `tool-box' of the modern day peptidominetic chemist, as well as providing a novel approach to the field of rational design. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Conformation; Foldamer; Peptidomimetics

Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Enantioselective syntheses of (-)-pinellic acid, alpha- and beta-dimorphecolic acid - Baruah, Pranjal K.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Tetrahedron, 2007)
An efficient enantioselective convergent approach for the synthesis of (-)-pinellic acid 1, alpha- and beta- dimorphecolic acid (2 and 3) from 1,9-nonane diol is described. The synthetic strategy features Sharpless asymmetric hydroxylation, Sonogashira coupling and Birch reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric dihydroxylation; influenza; Sonogashira coupling

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Steric control in pd-mediated cycloisomerization of sugar alkynols: documentation of a rare allylic epimerization - Ramana, Chepuri V.; Patel, Pitarnbar; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Pd-mediated cycloisomerization of C3-alkynylated glucofuranosyl derivatives revealed a dominance of steric factors over electronic factors. However, the intermediate glycals were epimerized prior to the ketalization and afforded the more stable cis-fused bicyclic ketals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bis-Homopropargylic Alcohols; Oriented Organic-Synthesis; Nucleophilic-Attack; Room-Temperature; Palladium; Chemistry; Heterocycles; Complexes; Transformations; Sonogashira

Total synthesis of pachastrissamine (jaspine B) enantiomers from D-glucose - Ramana, C. V.; Giri, Awadut G.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Synthesis of both enantiomers of pachastrissamine is described from a common chiral template. The stereoselective construction of the central tetrahydrofuran units was based on the pseudodesymmetrization of a pentodialdo-1,4-furanose derivative taking advantage of the latent symmetry present. (c) 2006 Published by Elsevier Ltd.
Keywords: 4-furanose; chiron approach; Ohira-Bestmann reaction; pachastrissamine/jaspine B; pentodialdo-1; ring isomerization

Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Di-tert-butyl N,N `-(octahydropentalene-2,5-diyl) dicarbamate - Kendhale, Amol M.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2008)
In the molecule of the title compound, C18H32N2O4, the central bicyclo[3.3.0] octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0] octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0] octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N-H center dot center dot center dot O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 angstrom).

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Expeditious one-step entry to the tetracyclic core of integrastatins - Ramana, C. V.; Reddy, Challa Nageswara; Gonnade, Rajesh G. (Chemical Communications, 2008)
Herein we describe a one-step assembly of structurally complex small molecules representing the central skeleton of integrastatins by employing a simple pinacol transform.

Ferrocene-linked thymine/uracil conjugates: base pairing directed self-assembly and supramolecular packing - Patwa, Amit N.; Gupta, Susmita; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2008)
Ferrocene-linked bis(nucleobase) (la-c) and chimeric nucleobase (1d) conjugates have been synthesized from mono- and bis(hydroxybutyl)ferrocene 6 via Mitsunobu reaction as the key step. X-ray crystallographic studies of ferrocene bis(nucleobase) conjugates reveal two-dimensional supramolecular organizations of backbones through self-assembled Watson-Crick and reverse Watson-Crick type pairs. Ferrocene-bis(thymine) conjugate self-assembles by reverse Watson-Crick pairing, while the corresponding bis(uracil) conjugate self-assembles by alternating WC and reverse WC type pairing. Such continuous assemblies are not seen in monosubstituted ferrocene nucleobase conjugates which form only planar sheets. The results are interesting from the point of understanding and engineering supramolecular assemblies through rational design of base pairing patterns.

Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding

Pre-organization-mediated macrocylization: efficient synthesis and structural investigations of BINOL-m-phenylenediamine-derived macrocycles - Srinivas, Deekonda; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This letter describes a serendipitous discovery of an efficient synthetic route to BINOL-m-phenylenediamine-derived macrocycles. These macrocycles are quickly accessible in an one-pot procedure by the direct condensation of (R) and (S) BINOL bis-acids with suitably substituted m-phenylenediamine analogs. Structural investigations by single crystal X-ray crystallography and solution-state NMR studies provided convincing evidence of their intramolecular hydrogen bonding arrangement and rigid structural architecture. The striking feature of these macrocycles is their ready accessibility in optically pure form coupled with their ease of synthesis. (C) 2008 Elsevier Ltd. All rights reserved.

Rigid bicyclo[3.3.0]octane (octahydropentalene): a heavily constrained novel aliphatic template for molecular self-assembly - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This Letter reports the utility of a heavily constrained cis-fused bicyclo[3.3.0]octane (octahydropentalene) aliphatic template for effecting molecular self-assembly. An attractive feature of this system is its heavily constrained alicyclic backbone that would allow for the exploration of self-assembling systems with conformationally ordered features. (C) 2008 Elsevier Ltd. All rights reserved.

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.

Design and synthesis of bile acid-based amino sterols as antimicrobial agents - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Shukla, Praveen K.; Gonnade, Rajesh G. (Bioorganic & Medicinal Chemistry Letters, 2009)
New bile acid-based amino sterols were synthesized in good yields from C-3 beta-oxiranes as key intermediates. These derivatives were evaluated for their in vitro antimicrobial properties against human pathogens. These compounds showed better antibacterial activity as compared to antifungal activity. Compounds 21 and 22 showed comparable antibacterial activity to gentamicin against Staphylococcus aureus with IC(50) values of 5.14 and 4.46 mu g/mL. This is the first report for the synthesis of C-3 beta-oxiranes on the steroids having A/B cis ring junction and these oxiranes have been used for the synthesis of amino sterols 17, 18, 21, and 22. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amino sterols; Antibacterial agent; bile acid; Oxirane

Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.

Enhancing intermolecular benzoyl-transfer reactivity in crystals by growing a ``reactive'' metastable polymorph by using a chiral additive - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2009)
Racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate, which normally crystallizes in a monoclinic form (form I, space group P2(1)/n) could be persuaded to crystallize out as a metastable polymorph (form II, space group C2/c) by using a small amount of either D- or L- 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate as an additive in the crystallization medium. The structurally similar enantiomeric additive was chosen by the scrutiny of previous experimental results on the crystallization of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate. Form II crystals call be thermally transformed to form I crystals at about 145 degrees C. The relative organization of the molecules in these dimorphs vary slightly in terms of the helical assembly of molecules, that is, electrophile (El)center dot center dot center dot nucleophile (Nu) and C-H center dot center dot center dot pi interactions, but these minor variations have a profound effect on the facility and specificity of benzoyl-group-transfer reactivity in the two crystal forms. While form II crystals undergo a clean intermolecular benzoyl-group-transfer reaction, form I crystals are less reactive and undergo non-specific benzoyl-group transfer leading to a Mixture of products. The role played by the additive in fine-tuning small changes that are required in the molecular packing opens up the possibility of creating new polymorphs that show varied physical and chemical properties. Crystals of D-2.6-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (additive) did not show facile benzoyl-group-transfer reactivity (in contrast to the corresponding racemic compound) due to the lack of proper juxtaposition and assembly of molecules.
Keywords: Acylation; carbohydrates; Crystal growth; cyclitols; solid-state reactions

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Magnetic phase transition in valence tautomers as polymorphs of 3-iodolawsone: Single crystal X-ray structure, DSC and EPR studies - Zaware, Santosh B.; Dagade-Waghmode, Shobha; Gonnade, Rajesh G.; Srinivas, Darbha; Rane, Sandhya Y. (Journal of Molecular Structure, 2009)
Three polymorphs of 3-iodolawsone (I-III) have been isolated and characterized by single crystal X-ray diffraction, electron paramagnetic resonance (EPR) spectroscopy and differential scanning calorimetry (DSC) techniques. Polymorphs I and II were crystallized from methanol in two different valence tautomeric forms: hydroxynaphthoquinone (HNQ) and hydroxynaphthoseimquinone (HNSQ) as needles and thick plates, respectively. Polymorph III was crystallized from ethanol in HNQ form, as thin plates Chiral crystals of I belongs to the orthorhombic P2(1)2(1)2(1) space group: II and III belong to the monochnic non-centrosymmetric space group Cc. The molecules are packed via O-H O bonding and pi . pi stacking interactions. The study reveals that relatively stronger intermolecular H-bonding (2.02 angstrom) and most favoured pi . pi stacking (similar to 3 49 angstrom) interactions lead II to HNSQ radicals, presence of which was confirmed by EPR (g = 2.0052) spectroscopy. Interestingly, these materials exhibit crystal-to-crystal magnetic phase transition from polymorph I (diamagnetic) to polymorph II (paramagnetic structure) at 171.1 degrees C as identified by DSC and X-ray crystallographic studies (C) 2009 Elsevier B.V. All rights reserved
Keywords: 3-Iodolawsone; Hydroxynaphthoquinone (HNQ); Hydroxynaphthosemiquinone radical (HNSQ); Magnetic phase transition; Polymorphs; Valence tautomers

Pd(II)-mediated alkynediol spiroketalization: first total synthesis of (-)-cephalosporolide E and (+)-cephalosporolide F - Ramana, C. V.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2009)
Herein we describe a concise assembly of the central 1.6-dioxaspiro[4.4]nonane core of cephalosporolides E/F by employing a Pd-mediated alkynediol cycloisomerization and their total synthesis. On the basis of spectroscopic data and optical rotation values, the absolute configurations of cephalosporolides E/F were proposed.

Stereoselective construction of steroidal side chain from 16-dehydropregnenolone acetate - Aher, Nilkanth G.; Gonnade, Rajesh G.; Pore, Vandana S. (Synlett, 2009)
Stereoselective construction of steroidal side chain at C-20 having `natural' configuration using 16-dehydropregnalone acetate (16-6PA) as a starting material has been carried out. Palladium-catalyzed carbon-carbon bond-forming Heck reaction between C-20 vinyl iodide with methyl acrylate and transfer hydrogenation with triethylsilane and Pd/C are the key steps for stereoselective side-chain synthesis.
Keywords: 16-dehydropregnenolone acetate; Heck coupling; stereoselectivity; steroidal side chain; transfer hydrogenation

Two modes of O-H center dot center dot center dot O hydrogen bonding utilized in dimorphs of racemic 6-O-acryloyl-2-O-benzoyl-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
The title compound, C(17)H(16)O(8), yields conformational dimorphs [forms (I) and (II)] at room temperature, separately or concomitantly, depending on the solvent of crystallization. The yield of crystals of form (I) is always much more than that of crystals of form (II). The molecule has one donor -OH group that can make intermolecular O-H center dot center dot center dot O hydrogen bonds with one of the two acceptor C O groups, as well as with the hydroxyl O atom; interestingly, each of the options is utilized separately in the dimorphs. The crystal structure of form (I) contains one molecule in the asymmetric unit and is organized as a planar sheet of centrosymmetric dimers via O H center dot center dot center dot O hydrogen bonds involving the OH group and the carbonyl O atom of the acryloyl group. In the crystal structure of form (II), which contains two independent molecules in the asymmetric unit, two different O-H center dot center dot center dot O hydrogen bonds, viz. hydroxyl-hydroxyl and hydroxyl-carbonyl (benzoyl), connect the molecules in a layered arrangement. Another notable feature is the transformation of form (II) to form (I) via melt crystallization upon heating to 411 K. The higher yield of form (I) during crystallization and the thermal transition of form (II) to form (I) suggest that the association in form (I) is more highly favoured than that in form (II), which is valuable in understanding the priorities of molecular aggregation during nucleation of various polymorphs.

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Ferrocene-Bis(thymine/uracil) conjugates: base pairing directed, spacer dependent self-assembly and supramolecular packing - Patwa, Amit N.; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2010)
X-ray crystallographic studies of methylene linked Ferrocene-bis(thymine/uracil) conjugates Fc(T:T)m and Fc(U:U)(M) reveal base dependent 2-D supramolecular assemblies generated via wobble self-pairing for bis-thymine and reverse wobble self-pairing for bis-uracil conjugates, differing in architecture from the corresponding butylene spacer linked conjugates

Helical self-assembly of molecules in pseudopolymorphs of racemic 2,6-di-O-(4-halobenzoyl)-myo-inositol 1,3,5-orthoformates: clues for the construction of molecular assemblies for intermolecular acyl transfer reaction - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2010)
The crystal structure of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate (1) which underwent a facile intermolecular benzoyl transfer reaction in the solid state, revealed a helical assembly of molecules along the two-fold screw axis via O-H center dot center dot center dot O hydrogen bond bringing the electrophile (C=O) and the nucleophile (-OH) in close proximity along the helical axis. However, structurally related racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (2) and chloro (3)) produced triclinic dimorphs (both P (1) over bar) when crystallized from methanol and ethyl acetate. Molecules in either form did not assemble spirally (like 1), and instead exhibited a one-dimensional isostructurality, bridging O-H center dot center dot center dot O linked identical molecular strings via C-H center dot center dot center dot O interactions across the inversion center. However, the molecules of 2 and 3 assembled in a helical manner similar to 1 with inclusion of solvent molecules in the crystal lattice when crystallized from other common organic solvents. Remarkably, in all the solvates the host molecules formed strikingly similar helices around the crystallographic 2(1)-screw axis through O-H center dot center dot center dot O bond involving the -OH group and carbonyl oxygen of the equatorial C2-O-benzoyl group. Comparison of the crystal structure of dimorphs and the solvatomorphs revealed that the solvent molecules, which interact with the orthoformate-bridge, trigger the helix formation of the host. The difference in the crystal structures of solvatomorphs arises in the interlinking of the neighbouring helices, which creates voids of different sizes to accommodate the solvent molecules. All the solvates crystallized in the monoclinic system distributed over three different space groups P2(1)/n, P2(1)/c and C2/c. In the P2(1)/n system, the adjacent helices are linked via C-X center dot center dot center dot O contacts, in P2(1)/c via C-H center dot center dot center dot X (X Cl, Br) contacts and in C2/c via short X center dot center dot center dot X contacts (X = Cl). The helical organization achieved through solvent mediation and inclusion is of significance in creating molecular packing for intermolecular acyl transfer reactions in crystals.

Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization

Synthesis, resolution, and applications of 3-amino-2,2-dimethy1-1,3-diphenylpropan-1-ol, a conformationally restricted 1,3-aminoalcohol - Patil, M. N.; Gonnade, Rajesh G.; Joshi, Navalkishore N. (Tetrahedron, 2010)
Efficient synthetic routes to both syn and anti diastereomers of a conformationally restricted 1,3-aminoalcohol were devised. Resolution of the aminoalcohols was accomplished through diastereomeric salt with R-(-)-O-acetyl mandelic acid. These aminoalcohols were examined as ligands for two standard reactions, namely, enantioselective addition of Et(2)Zn to aldehydes and reduction of prochiral ketones with BH(3). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-Aminoalcohol; Aldol-Tishchenko reaction; Diethylzinc; Oxazaborinane; Resolution

Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.

Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Halogen bonding in 2,5-dichloro-1,4-benzoquinone: insights from experimental and theoretical charge density analysis - Hathwar, Venkatesha R.; Gonnade, Rajesh G.; Munshi, Parthapratim; Bhadbhade, Mohan M.; Row, Tayur N. Guru (Crystal Growth & Design, 2011)
Experimental charge density distribution in 2, 5-dichloro-1, 4-benzoquinone has been carried out using high resolution X-ray diffraction data at 90 K to quantitatively evaluate the nature of C-Cl center dot center dot center dot O=C halogen bond in molecular crystals. Additionally, the halogen bond is studied from geometrical point of view and the same has been visualized using Hirshfeld surface analysis. The obtained results from experimental charge density analysis are compared with periodic quantum calculations using B3LYP 6-31G(d,p) level of theory. The topological values at bond critical point, three-dimensional static deformation density features and electrostatic potential isosurfaces unequivocally establish the attractive nature of C-Cl center dot center dot center dot O=C halogen bond in crystalline lattice.

Target cum flexibility: an alkyne [2+2+2]-cyclotrimerization strategy for synthesis of trinem library - Ramana, C. V.; Dushing, Mangesh P.; Mohapatra, Sradhanjali; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron Letters, 2011)
A rapid access to the central 4,5,6-tricyclic core of 4,5,6-trinems has been achieved by employing the alkyne [2+2+2]-cyclotrimerization as the key and final reaction in the synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Strength from weakness: the role of CH center dot center dot center dot N hydrogen bond in the formation of wave-like topology in crystals of aza-heterocycles - Shivakumar, Kota; Vidyasagar, Adiyala; Naidu, Andra; Gonnade, Rajesh G.; Sureshan, Kana M. (Crystengcomm, 2012)
Crystal engineering has succeeded in the design and construction of various architectures such as tapes, ribbons, rosettes, layers etc. Though wavy layer packing is known to occur in crystals, no crystal engineering attempts have been ventured to create wavy layer topology in crystals. Aromatic nitrogen heterocyclics (ANHs) are known to preferentially self assemble in lateral fashion through edge-to-edge CH center dot center dot center dot N hydrogen bonds. Exploiting this preferential lateral assembly of ANHs, we have engineered wavy layer architectures in the crystals of various substituted quinolines.

Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.

Topochemical click reaction: spontaneous self-stitching of a monosaccharide to linear oligomers through lattice-controlled azide-alkyne cycloaddition - Pathigoolla, Atchutarao; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2012)
Keywords: Click chemistry; green chemistry; polymerization; pseudosugars; topochemistry

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Asymmetric N-heterocyclic carbene (NHC)-catalyzed annulation of modified enals with enolizable aldehydes - Yetra, Santhivardhana Reddy; Kaicharla, Trinadh; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
N-Heterocyclic carbene (NHC)-catalyzed highly enantioselective lactonization of modified enals with enolizable aldehydes, proceeding via the alpha,beta-unsaturated acylazolium intermediates, is reported. The reaction results in the asymmetric synthesis of synthetically important 4,5-disubstituted dihydropyranones.

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Evaluation of viability of halogen•••O2N interactions: insight form crystal packing in a series of isomeric halo and nitro substituted triaryl compounds with modular positioning of halogen and NO2 groups - Ramana, Chepuri V.; Goriya, Yogesh; Durugkar, Kulbhushan A.; Chatterjee, Soumitra; Krishnaswamy, Shobhana; Gonnade, Rajesh G. (CrystEngComm, 2013)
A series of isomeric triaryl compounds with a modular positioning of the halogen and NO2 groups have been synthesized by the azide–alkyne “click reaction” and have been characterized by single crystal X-ray structure analysis. This isomeric series has provided an opportunity for understanding the efficiency of the bifurcated halogen⋯NO2 synthon in the organization of the molecules in the crystalline lattice. The changes in molecular conformation, crystal packing and supramolecular aggregation due to the change in the relative positioning of the complementary groups, halogen atom and the NO2 group on ring A and ring C respectively, have been discussed. All the isomers synthesized are crystalline and establish the triazole as a reliable linker for crystal engineering oriented molecular synthesis. The 2-NO2 derivatives display in general, a helical architecture and 3-NO2 derivatives exhibit a centrosymmetric dimeric assembly via the complementary C–H⋯O interactions leading to either a helical or a 2-dimensional sheet pattern. The molecular organization in 4-NO2 derivatives revealed in general a 2D sheet pattern.

Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Multicomponent reactions involving arynes, quinolines, and aldehydes - Bhunia, Anup; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
The multicomponent reaction involving arynes, quinolines, and aldehydes leading to the diastereoselective synthesis of benzoxazino quinoline derivatives in good yields proceeding via 1,4-zwitterionic intermediates is reported. In addition, the synthetic potential of various carbonyl compounds in this reaction as well as the utility of isoquinoline as the nucleophilic trigger has been examined.

Proline-catalyzed asymmetric synthesis of syn- and anti-1,3-diamines - Kumar, Pradeep; Jha, Vishwajeet; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2013)
A general organocatalytic strategy for asymmetric synthesis of both syn/anti-1,3-diamines has been developed. The strategy employs proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step where syn-1,3-diamine was obtained as the most favorable product.

Rhenium(I) tricarbonyl complex of 5,20-bis(p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin: first X-ray structural characterization of metal complex of 21-selenaporphyrin - Ghosh, Avijit; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dalton Transactions, 2013)
Synthesis and first structural characterization of hexa coordinated rhenium(I)tricarbonyl complex of 5,20-bis( p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin 3 are described. The Re(I)complex of 21-selenaporphyrin 3 was synthesized by treating free base 21-selenaporphyrin in 1,2-dichlorobenzene with Re(CO)(5)Cl at reflux for 7 h and analyzed using mass, NMR, FT-IR, UV-vis and electrochemical techniques. The first structure of metal complex of 21-selenaporphyrin was determined by X-ray single crystal analysis. The crystal structure revealed that the Re(CO)(3) coordinates to two of the three inner nitrogens and one selenium to produce compound 3. The selenophene ring bent towards the Re(I)ion and the selenium is displaced by 0.41 angstrom from the mean plane of 24-atoms to coordinate with Re(I)ion in eta(1)-fashion. The 21-selenaporphyrin is distorted in compound 3 compared to free base 21-selenaporphyrin. H-1 and C-13 NMR studies indicated that compound 3 exhibits fluxional behaviour in coordination mode of binding in solution. The compound 3 is highly stable and does not undergo decomplexation under acidic conditions. The absorption spectra showed three broad Q-bands and splitted Soret band and electrochemical studies indicated that compound 3 is stable under redox conditions.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Syntheses and determination of absolute configurations and biological activities of the enantiomers of the longtailed mealybug pheromone - Ramesh, Remya; Swaroop, Pandrangi Siva; Gonnade, Rajesh G.; Thirupath, Choppari; Waterworth, Rebeccah A.; Millar, Jocelyn G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2013)
Preparation and assignment of absolute configurations to both enantiomers of the sex pheromone of the longtailed mealybug, an irregular monoterpenoid with extraordinary biological activity, has been completed. Comparison of the biological activities of both enantiomers and the racemate in field trials showed that the (S)-(+)-enantiomer was highly attractive to male mealybugs, strongly suggesting that female longtailed mealybugs produce this enantiomer. The (R)-(-)-enantiomer was benign, being neither attractive nor inhibitory.

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones

Synthesis and structural studies of S-type/N-type-locked/frozen nucleoside analogues and their incorporation in RNA-selective, nuclease resistant 2 `-5 ` linked oligonucleotides - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Gonnade, Rajesh G.; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2013)
2'-endo locked or frozen (S-type)/3'-endo locked or frozen (N-type) nucleoside analogues were synthesized. Conformational analysis based on (3)J(HH) and NOE measurements is presented which is further confirmed by X-ray crystal structural studies. 2'-5' isoDNA oligonucleotides (ON) were synthesized using these modified nucleoside analogues and UV-T-m studies of the resultant 2'-5' isoDNA : RNA duplexes reflect the site-and sequence-dependent effects and confirm that the S-type sugar conformations were preferred over the N-type sugar geometry in such duplexes.

Synthesis of 3,5-Bis(acrylaldehyde) boron-dipyrromethene and application in detection of cysteine and homocysteine in living cells - Madhu, Sheri; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Journal Of Organic Chemistry, 2013)
Synthesis, characterization, and spectral and electrochemical properties of 3,5-bis(acrylaldehyde) BODIPY are described. The compound exhibited higher selectivity toward cysteine/homocysteine than toward other amino acids and thiol-containing compounds as shown by absorption and emission titration experiments and by experiments in living cells.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Triazole-linked anthracenyl-appended calix[4]arene conjugate as receptor for Co(II): synthesis, spectroscopy, microscopy, and computational studies - Mummidivarapu, V. V. Sreenivasu; Hinge, Vijaya Kumar; Tabbasum, Khatija; Gonnade, Rajesh G.; Rao, Chebrolu P. (Journal of Organic Chemistry, 2013)
A new triazole-linked anthracenyl-appended calix[4]arene-1,3-diconjugate (L) has been synthesized and characterized, and its single crystal XRD structure has been established. Binding properties of L toward different biologically relevant metal ions have been studied by fluorescence and absorption spectroscopy in ethanol. L exhibits selective recognition of Co2+ and can detect down to a concentration of 55 ppb (0.92 mu M). The roles of the calix[4]arene platform as well as the preorganized binding core in L's selective recognition have been demonstrated by studying appropriate control molecules. The mode of binding of L with Co2+ has been modeled both by DFT and MD computational calculations. L and its Co2+ complex could be differentiated on the basis of the nanostructural features observed in AFM and TEM.

Weak becomes strong: remarkable strength of C-H center dot center dot center dot pi hydrogen bond in the presence of O-H center dot center dot center dot O hydrogen bonds in the crystal stabilization - Sureshan, Kana M.; Gonnade, Rajesh G. (CrystEngComm, 2013)
We report crystallographic evidence for the significance of C-H center dot center dot center dot pi hydrogen bonds in the crystal stabilization of 1,4-di-O-benzoyl-myo-inositol. The strength of this otherwise weak hydrogen bond matches with the strength of O-H center dot center dot center dot O hydrogen bonds.

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Biocatalyst mediated functionalization of salannin, an insecticidal limonoid - Haldar, Saikat; Kolet, Swati P.; Dandekar, Devdutta S.; Kale, Balaji S.; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (RSC Advances, 2014)
Transformation of salannin, an insecticidal C-seco limonoid was investigated using a fungal system, Cunninghamella echinulata. Salannin was efficiently converted into two metabolites, where the C-17 furan moiety was transformed into gamma-hydroxybutenolide (salanninolide) and N-(2-hydroxyethyl)-alpha,beta-unsaturated-gamma-lactam (salanninactam) analogues. Present studies have indicated salanninolide to be a metabolite in the C-seco limonoid biosynthetic pathway.

Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.

Design and development of POCN-pincer palladium catalysts for C-H bond arylation of azoles with aryl iodides - Khake, Shrikant M.; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2014)
{Well-defined and efficient POCN-ligated palladium complexes have been developed for the direct C H bond arylation of azoles with aryl iodides. The phosphinite-amine pincer ligands 1-(R2PO)-C6H4-3-((CH2NPr2)-Pr-i) 1R2POCNIPr2-H; R = `Pr (1a)

Diels-alder reaction of tropones with arynes: synthesis of functionalized benzobicyclo[3.2.2]nonatrienones - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Bisht, Rajesh H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
A new procedure for the mild, practical, and scalable Diels–Alder reaction of tropones with arynes is reported. Differently substituted tropones undergo selective [4 + 2] cycloaddition with arynes generated in situ by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates, allowing the formation of functionalized benzobicyclo[3.2.2]nonatrienone derivatives in moderate to good yields. In addition, the photophysical properties of the cycloadducts are presented.

Efficient synthesis of 9-aryldihydrophenanthrenes by a cascade reaction involving arynes and styrenes - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
A mild, general, and transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes is reported. The aryne generated by the fluoride-induced,1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes an efficient cascade reaction initiated by the Diels-Alder reaction with the differently substituted styrenes leading to the formation of 9-aryl-9,10-dihydrophenanthrene derivatives in moderate to good yields.

General approach to N-heterocyclic carbenes with a fused tetracyclic core: ligands for suzuki-miyaura cross-coupling reaction - Sutar, Revannath L.; Kumar, Vinod; Shingare, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2014)
The synthesis of an N-heterocyclic carbene (NHC) based on a tetracyclic scaffold by using simple, general, and scalable chemistry is disclosed. The developed route is suitable for introducing multiple substitutions on the tetracyclic scaffold. The utility of the present NHC as a ligand in the Suzuki-Miyaura cross-coupling reaction is demonstrated with a low catalyst loading.
Keywords: C-C coupling; carbenes; Homogeneous catalysis; N ligands; synthetic methods

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Multicomponent reactions involving phosphines, arynes and aldehydes - Bhunia, Anup; Kaicharla, Trinadh; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Although nucleophilic phosphine-catalysis is a powerful tool for the construction of various carbocycles and heterocycles, the reactions in which phosphines are incorporated into the final product are rare, and the reports on phosphine addition to highly electrophilic arynes are scarce. Herein, we report the phosphine triggered multicomponent reaction of arynes and aldehydes, which takes place via the formal [3+2] cycloaddition of an initially generated 1,3-phosphonium zwitterion from phosphines and arynes with aldehydes. The reaction resulted in the formation of a diverse range of stable pentacovalent phosphoranes in good yields based on the benzooxaphosphole system.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of functionalized cyclopentenes via alpha,beta-unsaturated acyl azoliums - Mondal, Santigopal; Yetra, Santhivardhana Reddy; Patra, Atanu; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Highly enantioselective NHC-organocatalyzed synthesis of functionalized cyclopentenes proceeding via alpha,beta-unsaturated acyl azolium intermediates is reported. The organocascade reaction of modified enals with malonic ester derivatives having a gamma-benzoyl group involves the Michael-intramolecular aldol-beta-lactonization-decarboxylation sequence to deliver cyclopentenes in good yields and excellent ee values.

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Stereospecific synthetic approach towards tamiflu using the ramberg-backlund reaction from cysteine hydrochloride - Chavan, Subhash P.; Chavan, Prakash N.; Gonnade, Rajesh G. (RSC Advances, 2014)
The stereospecific formal synthesis of Tamiflu from L-cysteine hydrochloride as the chiral source is described. The notable feature of the present strategy is the Ramberg-Backlund reaction and Sharpless-Reich protocol as the key chemical transformations to access the cyclohexene skeleton of Tamiflu.

Synthesis, structure, spectral, electrochemical and sensing properties of 3-amino boron-dipyrromethene and its derivatives - Ganapathi, Emandi; Madhu, Sheri; Chatterjee, Tamal; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dyes and Pigments, 2014)
We report the synthesis of 3-amino boron-dipyrromethene (3-amino BODIPY) by treating 3-bromo boron-dipyrromethene (3-bromo BODIPY) initially with sodium azide in acetonitrile followed by tri-phenylphosphine(PPh3)/H2O in tetrahydrofuran in three steps under mild reaction conditions. In this reaction, 3-azido BODIPY which formed in the first step was not isolated but the 3-iminophosphorane BODIPY which formed in the second step was isolated and characterized crystallographically. The 3-amino BODIPY was characterized by various spectroscopic and X-ray analytical techniques. To test the reactivity of amine functionality on BODIPY core, we prepared 1-(meso-anisyl BODIPY)-3-phenyl urea/thiourea derivatives under simple reaction conditions. Our studies indicated that 1-(meso-anisyl BODIPY)-3-pheny thiourea can act as specific chemodosimetric sensor for Hg2+ ion and 1-(meso-anisyl BODIPY)-3-phenyl urea as colorimetric and ratiometric sensor for F- ion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: 3-Amino boron dipyrromethene; Chemodosimeter; F sensor; Fluorescent probes; Iminophosphorane BODIPY; Mercury(II) sensor

Asymmetric vinylogous michael reaction of cyclic enones with silyloxy furans - Jadhav, Amol P.; Rao, V. U. Bhaskara; Singh, Pradeep; Gonnade, Rajesh G.; Singh, Ravi P. (Chemical Communications, 2015)
The asymmetric vinylogous Michael reaction of cyclohexenone/medium and large cyclic enones with 2-silyloxyfuran is still a synthetic challenge. In this report, we have explored 1,4-conjugate addition of an enantioselective chiral, primary diamine catalyzed, 2-silyloxy furan to various cyclic enones and beta-substituted cyclic enones. The reaction provided syn-Michael adducts (cycloalkane connected gamma-butenolide) with good yields, diastereo and enantioselectivities. Furthermore, the synthetic potential of these syn-Michael adducts is demonstrated by 1,4-addition of nucleophiles on the butenolide substructure.

Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction

Diastereoselective synthesis of cyclopentanone-fused spirooxindoles by N-heterocyclic carbene-catalyzed homoenolate annulation with isatilidenes - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Chemistry Frontiers, 2015)
N-Heterocyclic carbene (NHC)-catalyzed formal [3 + 2] annulation of α,β-unsaturated aldehydes with N-substituted isatilidenes resulting in the diastereoselective synthesis of cyclopentanone-fused spirooxindoles is demonstrated. Mechanistically, the reaction proceeds via the generation of homoenolate equivalent intermediates from NHC and enals, which on interception with isatilidenes afford spiroheterocyclic compounds bearing an all-carbon quaternary spiro-center in moderate to good yields and generally with high diastereoselectivity. Moreover, the functionalization of the spirooxindoles as well as the initial studies on the enantioselective version of this reaction are presented.

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Enantiospecific synthesis of both enantiomers of the longtailed mealybug pheromone and their evaluation in a new zealand vineyard - Ramesh, Remya; Bell, Vaughn; Twidle, Andrew M.; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2015)
The irregular monoterpenoid sex pheromone of Pseudococcus longispinus and its enantiomer were prepared from the corresponding bornyl acetates. The use of readily accessible chiral starting materials and lactone lactone rearrangement are the highlights of the present synthesis. The biological activities of the two enantiomers and racemic mixture were tested in a New Zealand vineyard. The (S)-(+)-enantiomer was significantly more attractive to P. longispinus males than the racemic mixture or the (R)-(-)-enantiomer.

Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).

Furosemide cocrystals with pyridines: an interesting case of color cocrystal polymorphism - Sangtani, Ekta; Sahu, Sanjay Kumar; Thorat, Shridhar H.; Gawade, Rupesh L.; Jha, Kunal K.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2015)
Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4'-bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol-water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form II, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks were obtained after 1-2 days from the same flask, indicating that yellow needles were formed faster and the orange blocks were perhaps formed under thermodynamic conditions. Form 1I cocrystals could also be produced from the variety of common solvents. Cocrystallization of FS with 2,2'-bipyridine (2BPY) and 4-aminopyridine (4AP) gave colorless cocrystals 2 and 3, respectively, and did not exhibit polymorphism. The single-crystal X-ray structures, powder X-ray diffraction, photophysical characterization, differential scanning calorimetry, hot stage microscopy studies, and density functional theory (DFT) calculations provide insight into the structure property relationship. The common structural features observed in all of the structures is the formation of sandwich motifs comprising FS and pyridines through pi-stacking interactions. These motifs are linked differently through hydrogen bonding interactions in all three directions. The significant color difference between the two cocrystals dimorphs could be attributed to the different pi-stacking patterns and hydrogen bonding interactions between molecules of FS and 4BPY in their cocrystal structures. Investigation on the origin of the color difference using DFT calculations revealed the decrease in HOMO-LUMO gap for form 1II cocrystals (orange) compared to form 1I crystals (light yellow). The crystal-to-crystal thermal transformation of form 1I crystals to form 1II crystals of 1 suggests the role of pi-stacking assemblies in driving the self-assembly.

Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.

Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.

Insertion copolymerization of difunctional polar vinyl monomers with ethylene - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Chikkali, Samir H. (ACS Macro Letters, 2015)
A single-step synthesis, structural characterization and application of a neutral, acetonitrile ligated, palladium-phosphinesulfonate complex [{P<\^>O}PdMe(L)] (P<\^>O = K-2-P,O Ar2PC6H4SO2O with Ar = 2-MeOC6H4; L = CH3CN) (3) in coordination/insertion copolymerization of ethylene with difunctional olefin is investigated. In a significant development, complex 3 was found to catalyze insertion copolymerization of industrially relevant 1,1-disubstituted difunctional vinyl monomers for the first time. Thus, insertion copolymerization of ethyl-2-cyanoacrylate (ECA or super glue) and trifluoromethyl acrylic acid (TFMAA) with ethylene produced the corresponding copolymers with 6.5% ECA and 3% TFMAA incorporation. Increasing the concentration of difunctional olefins led to higher incorporation but at the expense of lower activities. These observations indicate that complex 3 tolerates difunctional vinyl monomers and provides direct access to difunctional polyolefins that have not been attempted before.

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis

Mono- and binuclear palladacycles via regioselective C-H bond activation: syntheses, mechanistic insights and catalytic activity in direct arylation of azoles - Pandey, Dilip K.; Khake, Shrikant M.; Gonnade, Rajesh G.; Punji, Benudhar (RSC Advances, 2015)
{Regioselective C-H bond palladation of the hybrid pincer-type ligands, 3-R2PO-C6H4-1-(CH2NPr2)-Pr-i [(POCNiPr2)-P-R2-H; R = Ph (1a)

N-Heterocyclic carbene-catalyzed diastereoselective synthesis of β-lactone-fused cyclopentanes using homoenolate annulation reaction - Mukherjee, Subrata; Mondal, Santigopal; Patra, Atanu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
NHC-catalyzed annulation of enals with 2-enoylpyridines or 2-enoylpyridine N-oxides leading to the diastereoselective synthesis of β-lactone-fused cyclopentanes is reported. The reaction proceeds via the generation of homoenolate equivalent intermediates and tolerates a broad range of functional groups.

Novel one-pot multi-component synthesis of 3,3 `-disubstituted oxindole and spirooxindole scaffolds via Sn-catalyzed C(sp(3))-H functionalization of azaarenes by sequential Knoevenagel-Michael-cyclization reaction - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek Abdul Rashid (RSC Advances, 2015)
Sn-catalyzed C(sp(3))-H bond functionalization of 2-methyl azaarenes/2-(azaaryl)methanes has been achieved for the first time in a one-pot multi-component reaction with isatin and active methylene compounds via tandem sequential Knoevenagel-Michael-intramolecular C-N cyclization. This strategy provides new cost-effective access to potent and biologically/medicinally important spirooxindoles/3,3'-disubstituted 2-oxindoles in good to excellent yields.

Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.

Preferential enrichment of DL-leucine using cocrystal formation with oxalic acid under nonequilibrium crystallization conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Morita, Yoko; Gonnade, Rajesh G.; Iwama, Sekai; Tsue, Hirohito; Tamura, Rui (Chirality, 2015)
By utilizing the preferential enrichment (PE) technique, we achieved an improved enantiomeric resolution of DL-leucine (Leu) using a 1:1 cocrystal (DL-1) of DL-Leu and oxalic acid. The crystal structure analysis of DL-1 indicated the occurrence of a novel type of phase transition and subsequent preferential redissolution of one enantiomer from the resulting crystals into solution. Chirality 27:405-410 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: chiral resolution; cocrystal formation; leucine; phase transition; preferential enrichment

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Synthesis, DNA interaction and anticancer activity of 2-anthryl substituted benzimidazole derivatives - Sontakke, Vyankat A.; Kate, Anup N.; Ghosh, Sougata; More, Piyush; Gonnade, Rajesh G.; Kumbhar, Navanath M.; Kumbhar, Anupa A.; Chopade, Balu Ananda; Shinde, Vaishali S. (New Journal of Chemistry, 2015)
2-Anthryl benzimidazole derivatives (5-7) with hydrogen, carboxyl and benzoyl substituents at the 5th position have been synthesized using a silica supported periodic acid catalyst. The DNA cleavage activity of 5-7 was studied in the presence of light using pBR322 plasmid DNA and was shown to vary with substitution at the 5th position of benzimidazole derivatives. DNA binding studies using ethidium bromide displacement assay demonstrated the non-intercalative binding mode of 5-7. The anticancer activity of these target molecules was tested against MCF-7 and HL-60 cell lines, and they exhibited remarkable activity in the micromolar range. Cellular uptake and morphological changes were confirmed by fluorescence and confocal microscopy. A molecular docking study was carried out to explore the DNA binding mechanism of 5-7.

Synthesis of naturally occurring (+)-osmundalactone and 4-epi-(+)-osmundalactone from triacetyl-O-D-glucal - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (+)-osmundalactone 1 has been achieved starting from readily available triacetyl-O-D-glucal 6 employing Ferrier rearrangement and Jones oxidation as key steps. Also, synthesis of 4-epi-(+)-osmundalactone 2 was accomplished from the common key intermediate 9. The absolute stereochemistry of (+)-osmundalactone 1 and a precursor of 4-epi-(+)-osmundalactone 2 have been established by single crystal X-ray analysis. The overall yield of compound 1 and 2 from triacetyl-O-D-glucal 6 is 13% and 8%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bioactive molecules; carbohydrates; D-glucal; Ferrier rearrangement; Pyrones

Synthesis of novel N-cyclopentenyl-lactams using the aube reaction - Shinde, Madhuri V.; Ople, Rohini S.; Sangtani, Ekta; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Beilstein Journal of Organic Chemistry, 2015)
A novel and convenient method utilizing the Aube reaction to access a new class of compounds that are similar to carbocyclic nucleosides is reported. The azido alcohol derived from Vince lactam undergoes the Aube reaction with various cyclic ketones to give cyclopentenyl-substituted lactams. Upon dihydroxylation, this affords the N-cyclopentenyl-lactam compounds in racemic form. Given the numerous uses of nucleosides and related compounds, we were interested in the synthesis of carbocylic nucleoside mimics. The attempts and results are described herein.
Keywords: Aube reaction; Biological activity; carbocyclic nucleosides; cyclopentenylated lactams; cyclopentylated lactams

Terahertz spectroscopy and solid-state density functional theory calculations of cyanobenzaldehyde isomers - Dash, Jyotirmayee; Ray, Shaurnik; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin B.; Gonnade, Rajesh G.; Ambade, Ashootosh V.; Joshi, Kavita; Pesala, Bala (Journal of Physical Chemistry A, 2015)
Spectral signatures in the terahertz (THz) frequency region are mainly due to bulk vibrations of the molecules. These resonances are highly sensitive to the relative position of atoms in a molecule as well as the crystal packing arrangement. To understand the variation of THz resonances, THz spectra (2-10 THz) of three structural isomers: 2-, 3-, and 4-cyanobenzaldehyde have been studied. THz spectra obtained from Fourier transform infrared (FTIR) spectrometry of these isomers show that the resonances are distinctly different especially below 5 THz. For understanding the intermolecular interactions due to hydrogen bonds, four molecule cluster simulations of each of the isomers have been carried out using the B3LYP density functional with the 6-31G(d,p) basis set in Gaussian09 software and the compliance constants are obtained. However, to understand the exact reason behind the observed resonances, simulation of each isomer considering the full crystal structure is essential. The crystal structure of each isomer has been determined using X-ray diffraction (XRD) analysis for carrying out crystal structure simulations. Density functional theory (DFT) simulations using CRYSTAL14 software, utilizing the hybrid density functional B3LYP, have been carried out to understand the vibrational modes. The bond lengths and bond angles from the optimized structures are compared with the XRD results in terms of root-mean-square-deviation (RMSD) values. Very low RMSD values confirm the overall accuracy of the results. The simulations are able to predict most of the spectral features exhibited by the isomers. The results show that low frequency modes (<3 THz) are mediated through hydrogen bonds and are dominated by intermolecular vibrations.

Three-component coupling involving arynes, aromatic tertiary amines, and aldehydes via aryl-aryl amino group migration - Bhojgude, Sachin Suresh; Baviskar, Dnyaneshwar R.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2015)
The transition-Metal-free multicomponent coupling of arynes, aromatic tertiary amines, and aldehydes proceeding via the aryl to aryl amino group migration has been demonstrated. This protocol allows rapid access to ortho-functionalized tertiary amines in moderate to good yields. Moreover, activated ketones can also be used as the aldehyde Component in the present reaction. The similarity of the aryl-aryl tertiary amino group migration with the Smiles rearrangement is striking.

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides - Ingole, Tukaram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2016)
This paper describes the consequences of incorporating a constrained heterocyclic aromatic b-amino acid 3-aminothiophenecarboxylic acid (3-Atc) into peptides containing beta-turn forming elements such as Pro-Gly motif and the effect on the secondary structural architecture of the entire peptide backbone. Conformational investigations of oligomers comprising an alpha,beta,alpha peptide sequence were carried out by single-crystal X-ray diffraction, solution-state NMR, nOe-restrained MD simulation and circular dichroism studies. The results suggested that these peptide sequences assume helical architecture. The helical folding in the oligomers was found to be devoid of inter-residual H-bonding, instead found to be stabilized by a co-operative effect of 6-membered H-bonding within the 3-Atc unit and conformational restrictions of individual amino acids in the peptide backbone.

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Application of roof-shape amines as chiral solvating agents for discrimination of optically active acids by NMR spectroscopy: study of match-mismatch effect and crystal structure of the diastereomeric salts - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (Journal of Organic Chemistry, 2016)
Optically active roof-shape amines were prepared and scanned as chiral solvating agents to study molecular recognition of acids by NMR analysis. Three types of amines were studied to establish a match mismatch effect for structurally diverse acid analytes. Single-crystal X-ray diffraction analysis was performed on the diastereomeric salts of roof shape amines and both isomers of mandelic acid to establish molecular conformation and correlate the absolute configuration with the observed NMR shift. The present system also recognizes the two isomers of weakly acidic BINOL and its derivatives.

Aryne [2,3] stevens rearrangement - Roy, Tony; Thangaraj, Manikandan; Kaicharla, Trinadh; Kamath, Rupa V.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
Arynes are employed in the transition-metal-free and mild [2,3] Stevens rearrangement of tertiary allylic amines for the synthesis of functionalized homoallylic amines in moderate to good yield with a broad substrate scope. The key nitrogen ylide intermediate was generated by the N-arylation of allyl amines using arynes. Moreover, the reaction of chiral allyl amines with arynes resulted in the enantiospecific synthesis of homoallylic amines. In addition, preliminary studies on the [1,2] Stevens rearrangement is also presented.

Au(I)/Ag(I) co-operative catalysis: interception of Ag-bound carbocations with α-gold(I) enals in the imino-alkyne cyclizations with N-allenamides - Bagle, Pradip N.; Mane, Manoj V.; Vanka, Kumar; Shinde, Dinesh R.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2016)

Benz–amidinato stabilized a monomeric calcium Iodide and a lithium calciate(II) cluster featuring group 1 and group 2 elements - Yadav, Sandeep; Swamy, V. S. V. S. N.; Gonnade, Rajesh G.; Sen, Sakya S. (ChemistrySelect, 2016)
Soluble calcium halides reported so far are mostly dimeric in nature. The halides occupy the bridging position and thus provide additional coordination to the metal. We obtained a monomeric calcium iodide [{PhC(NiPr)(2)} CaI(thf)(3)] (1) from the reaction of [PhC(NiPr)(2)] Li with Cal(2) in THF. The compound has been stabilized by electronic donation and steric shielding from the amidinate ligand as well as coordination of three THF molecules. 1 does not show any propensity towards ligand exchange reaction. When the same reaction is carried out in diethyl ether instead of THF, it led to the formation of a Li calciate(II) cluster of composition L2Ca4I8Li4O (L= PhC(NiPr)(2)) (2) with an encapsulated O2+ in the middle of a tetrahedron spanned by four Ca2+ ions. 2 represents a metal-rich halide comprising of both alkali and alkaline earth metals which is quite unprecedented. Another notable aspect is that the amidinate ligand binds to the calcium atom in chelating bidentate mode in 1, whereas in 2 each N atom of the amidinate ligands binds to two Ca atoms leading to bridging bis-chelating coordination mode.

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Engineering crystals that facilitate the acyl-transfer reaction: insight from a comparison of the crystal structures of myo-inositol-1,3,5-orthoformate-derived benzoates and carbonates - Tamboli, Majid I.; Krishanaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Structural Chemistry, 2016)
Minor variations in the molecular structure of constituent molecules of reactive crystals often yield crystals with significantly different properties due to altered modes of molecular association in the solid state. Hence, these studies could provide a better understanding of the complex chemical processes occurring in the crystalline state. However, reactions that proceed efficiently in molecular crystals are only a small fraction of the reactions that are known to proceed (with comparable efficiency) in the solution state. Hence, for consistent progress in this area of research, investigation of newer reactive molecular crystals which support different kinds of reactions and their related systems is essential. The crystal structures and acyl-transfer reactivity of a myo-inositol-1,3,5-orthoformate-derived dibenzoate and its carbonate (4-O-benzoyl-2-O-phenoxycarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O9) and thiocarbonate (4-O-benzoyl-2-O-phenoxythiocarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O8S) analogs are compared with the aim of understanding the relationship between crystal structure and acyl-transfer reactivity. Insertion of an O atom in the acyl (or thioacyl) group of an ester gives the corresponding carbonate (or thiocarbonate). This seemingly minor change in molecular structure results in a considerable change in the packing of the molecules in the crystals of myoinositol-1,3,5-orthoformate-derived benzoates and the corresponding carbonates. These differences result in a lack of intermolecular acyl-transfer reactivity in crystals of myo-inositol-1,3,5-orthoformate-derived carbonates. Hence, this study illustrates the sensitivity of the relative orientation of molecules, their packing and ensuing changes in the reactivity of resulting crystals to minor changes in molecular structure.

Experimental and computational analysis of supramolecular motifs involving C-sp2(aromatic)-F and CF3 groups in organic solids - Panini, Piyush; Gonnade, Rajesh G.; Chopra, Deepak (New Journal of Chemistry, 2016)
A detailed experimental (SCXRD) and theoretical (PIXEL and QTAIM) investigation of the evolution of different supramolecular motifs formed via the presence of both C(sp(2))/(sp(3))-F groups in the crystal packing has been performed in a series of newly synthesized substituted benzanilides (containing ``both'' the fluorine and the trifluoromethyl group in the same molecule) along with previously reported similarly related crystal structures [CrystEngComm, 2008, 10, 54-67; CrystEngComm, 2012, 14, 1972-1989, CrystEngComm, 2013, 15, 3711-3733]. It was observed that the highest stabilized molecular motifs primarily consist of C(sp(2))-H center dot center dot center dot F-C(sp(2)) H-bonds in preference to C(sp(2))-H center dot center dot center dot F-C(sp(3)) H-bonds in the crystal. The motifs involving C(sp(2))-H center dot center dot center dot F-C(sp(2))/(sp(3)) H bonds were observed to be present over the entire distance range between 2.2 and 2.7 angstrom, albeit the difference in energies of stabilization involving fluorine atoms attached to sp(2) and sp(3) carbon is not significant in molecular crystals. From QTAIM analysis, the C(sp(2))/(sp(3))-F center dot center dot center dot F-C(sp(2))/(sp(3)) interactions were observed to be a closed shell in nature and provide local stabilization, indicating the formation of bonds, similar to weak hydrogen bonds observed in crystals.

Impact of modular substitution on crystal packing: the tale of two ureas - Koshti, Vijay S.; Thorat, Shridhar H.; Gote, Ravindra P.; Chikkali, Samir H.; Gonnade, Rajesh G. (CrystEngComm, 2016)

Lewis acid catalyzed selective reactions of donor-acceptor cyclopropanes with 2-naphthols - Kaicharla, Trinadh; Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
Lewis acid-catalyzed reactions of 2-substituted cyclopropane 1,1-dicarboxylates with 2-naphthols is reported. The reaction exhibits tunable selectivity depending on the nature of Lewis acid employed and proceed as a dearomatization/rearomatization sequence. With Bi(OTf)(3) as the Lewis acid, a highly selective dehydrative [3+2] cyclopentannulation takes place leading to the formation of naphthalene-fused cyclopentanes. Interestingly, engaging Sc(OTf)(3) as the Lewis acid, a Friedel-Crafts-type addition of 2-naphthols to cyclo-propanes takes place, thus affording functionalized 2-naphthols. Both reactions furnished the target products in high regioselectivity and moderate to high yields.
Keywords: annulations; arenes; Lewis acids; reaction mechanisms; small ring systems

Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.

Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.

Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.

Synthesis of functionalized amino epoxides by a three-component coupling involving aziridines, arynes and aldehydes - Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2016)
A transition-metal-free three-component coupling involving N-substituted aziridines, arynes and aldehydes resulting in the formation of trisubstituted N-aryl alpha-amino epoxides has been demonstrated. The reaction likely proceeds via the highly strained cyclic nitrogen ylide intermediates generated from aziridines and arynes.

Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Total synthesis of isocladosporin and 3-epi-isocladosporin - Mohapatra, Debendra K.; Maity, Saurabh; Banoth, Shivalal; Gonnade, Rajesh G.; Yadav, J. S. (Tetrahedron Letters, 2016)
A convergent total synthesis of isocladosporin and 3-epi-isocladosporin is reported starting from commercially available homoallyl alcohol in 10 longest linear steps with 28% overall yield. The key steps involved in the synthesis are cross-metathesis, tandem isomerization followed by C-O and C-C bond formation reactions for the synthesis of trans-2,6-disubstituted dihydropyrans developed by us, acylation reaction and Luche reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylation reaction; Cross-metathesis; Iodocyclization; Isocladosporin 3-epi-Isodadosporin; Luche reduction

Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.

Base-free and catalyst-free synthesis of functionalized dihydrobenzoxazoles via vinylogous carbonate to carbamate rearrangement - Das, Tamal Kanti; Mondal, Santigopal; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
An unexpected, catalyst-free, and base-free intramolecular cyclization of N-aryloxyacrylate aldimines, under thermal conditions leading to the synthesis of functionalized dihydrobenzoxazoles, is reported. The reaction features a unique rearrangement of vinylogous carbonates to vinylogous carbamates resulting in a new carbon–oxygen and carbon–nitrogen bond construction. The reaction tolerates a broad range of functional groups and the desired products are formed in moderate to good yields.

Biomimetic total synthesis of angiopterlactone B and other potential natural products - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic Letters, 2017)
A one-pot biomimetic synthesis of (-)-angiopterlactone B and its enantiomer (+)-angiopterlactone B has been accomplished via TBAF-catalyzed tandem ring contraction followed by oxa-Michael/Michael addition sequence. Comparison of specific optical rotations, absolute configurations, and CD spectra of natural, synthesized (-)-angiopterlactone B and (+)-angiopterlactone B unequivocally proves that the isolated angiopterlactone B must be levorotatory. Synthesis of hitherto undiscovered natural products 18 and 20 and analogues of angiopterlactone B demonstrate the versatility of this method.

Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Development of (quinolinyl)amido-based pincer palladium complexes: a robust and phosphine-free catalyst system for C–H arylation of benzothiazoles - Pandiri, Hanumanprasad; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2017)
(Quinolinyl)amido-ligated palladium(II) complexes have been synthesized and applied in the catalytic C–H bond arylation of benzothiazoles. The tridentate ligand precursors R2N-C(O)CH2-(NH)-C9H6N [(R2NNN8-Q)–H; R2N = morpholinyl, Me-N-piperazinyl] and the pincer palladium complexes [κN,κN,κN-{R2N-C(O)CH2-(μ-N)-C9H6N}]PdX [(R2NNN8-Q)PdX {R2N = Et2N, morpholinyl, Me-N-piperazinyl; X = OAc or Cl}] were efficiently synthesized, and characterized by various analytical techniques. The iodo derivative (Et2NNN8-Q)PdI was obtained in excellent yield by the treatment of the complex (Et2NNN8-Q)PdCl with KI. The molecular structures of complexes (Et2NNN8-Q)Pd(OAc) (2a), (Et2NNN8-Q)PdCl (3a) and (Et2NNN8-Q)PdI (4a) were elucidated by X-ray crystallography. Complex 3a was found to be the most efficient catalyst for direct C–H bond arylation of substituted benzothiazoles with diverse aryl iodides using a mild base, K2CO3. The working catalyst system 3a is highly robust and can be recycled and reused several times for the arylation of benzothiazole without loss of catalytic activity. Preliminary mechanistic investigations using controlled studies and kinetic analysis have been performed, which greatly support a molecular mechanism for the arylation.

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles

H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.

Intramolecular ipso-arylative cyclization of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts through merged gold/visible light photoredox catalysis - Bansode, Avinash H.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2017)
A visible-light-promoted merged gold/photoredox catalyzed ipsoarylative cyclization has been reported. For instance, the reaction of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts in the presence of catalytic amounts of [(4-OCH3)C6H4](3)PAuCl and Ru(bpy)(3)(PF6)(2) under irradiation using a 32WCFL bulb gave arylated spirocarbocycles in moderate to good yields.

Lewis acid catalyzed cascade annulation of alkynols with alpha-ketoesters: a facile access to gamma-spiroketal-gamma-lactones - Kambale, Digambar A.; Thorat, Sagar S.; Pratapure, Madhukar S.; Gonnade, Rajesh G.; Kontham, Ravindar (Chemical Communications, 2017)
A novel Lewis acid catalyzed intermolecular cascade annulation of alkynols with alpha-ketoesters has been developed. This simple and efficient cascade annulation proceeds through a 5-exo-dig cyclization of alkynols followed by annulation with alpha-ketoester to provide a wide variety of unsaturated gamma-spiroketal-gamma-lactones (1,6-dioxaspiro[4.4]non-3-en-2-ones) related to many natural products.

Modular approach towards functionalized highly stable self-complementary quadruple hydrogen bonded systems - Rayavarapu, Suresh; Kheria, Sanjeev; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2017)
Self-complementary quadruple hydrogen bonded systems have shown potential as key building blocks for developing various supramolecular polymers. Opportunities for the introduction of multiple functionalities would further augment, in principle, their application potential. Herein, we report a novel modular approach to simultaneously introduce two closely aligned side chains into AADD-type self-complementary quadruple hydrogen-bonding systems. Dithiane-tethered ureidopyrimidinone has been used as a reactive intermediate to efficiently attach closely aligned side chains by simply reacting with amines to form highly stable molecular duplexes. These duplexes featuring AADD-type arrays of hydrogen bonding codes are highly stable in non-polar solvents (K-dim > 1.9 x 10(7) M-1 in CDCl3) as well as in polar solvents (K-dim > 10(5) in 10% DMSO-d(6)/CDCl3). Another notable feature of these self-assembling systems is their insensitivity to prototropy-related issues owing to their prototropic degeneracy, which will enhance their application potential in supramolecular chemistry.

Organocatalytic enantioselective vinylogous michael-aidoi cascade for the synthesis of spirocyclic compounds - Mondal, Santigopal; Mukherjee, Subrata; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
Enantioselective synthesis of pyrazolone-fused spirocyclohexenols by the secondary amine-catalyzed cascade reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones is reported. This formal [3 + 3] organocascade reaction proceeds through a vinylogous Michael-aldol sequence to furnish the spiroheterocycles with three stereocenters including an all-carbon quaternary center in good yields and selectivities. The catalytic generation of alpha,beta-unsaturated iminium ions from enals and tandem dienolate/enolate formation from pyrazolinones are the key for the success of this spiroannulation reaction.

Polymorphs and cocrystals: a comparative analysis - Gonnade, Rajesh G.; Sangtani, Ekta (Journal of the Indian Institute of Science, 2017)
Controlling polymorphism has been the subject of vigorous research in the recent past in the pharmaceutical industry due to the distinct physicochemical properties associated with each solid form. Developing cocrystals/salts of active pharmaceutical ingredients (APIs) has gained tremendous research interest in recent years owing to their potential to improve pharmaceutically relevant properties without affecting therapeutic efficacy. It is observed that compounds that exhibit polymorphism and also contain several H bond donor/acceptor groups have a tendency to form cocrystals and sometime even display cocrystal polymorphism, although this tendency cannot be generalized. The aim of this contribution is to correlate crystal structures of some polymorphic APIs and their respective cocrystals to understand the rationale behind a polymorphic compound generating cocrystals. Here, we make an attempt to compare how the conformation of the molecule observed in its polymorphs support the generation of cocrystals/salts. We understand that it is impossible to cover all the polymorphs and their cocrystals/salts available in the CSD; the comparative study has been carried out with a few case studies, wherein APIs displayed polymorphism (conformation) and also formed cocrystals/salts.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Salts and cocrystals of furosemide with pyridines: differences in π-Stacking and color polymorphism - Sangtani, Ekta; Mandal, Suman Kumar; Sreelakshmi, A. S.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Furosemide (FS), a loop diuretic drug that has a potential to exhibit polymorphism, produced color polymorphs of orange (form 1I) and yellow (form 1II) concomitantly with coformer 1, 2-bis(4-pyridyl)ethylene. However, cocrystallization of FS with other pyridines yielded colorless salts (2 and 4) and cocrystals (3 and 5). The significant color difference between the two polymorphs (forms 1I and 1II) could be attributed to the dissimilar π-stacking patterns between the two components and differences in their highest occupied molecular orbital−lowest unoccupied molecular orbital gap. The molecular packing of form 1I and 2 is very similar, but 2 is colorless due to lack of extended π-conjugation.

Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.

Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Unprecedented solvent induced inter-conversion between monomeric and dimeric silylene-zinc iodide adducts - Yadav, Sandeep; Sangtani, Ekta; Dhawan, Diksha; Gonnade, Rajesh G.; Ghosh, Debashree; Sen, Sakya S. (Dalton Transaction, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Usually, when a silylene reacts with a transition metal Lewis acid, it forms an adduct which could be either monomeric or dimeric. However, we present here that a silylene, [PhC(NtBu)(2)SiN(SiMe3)(2)] can form both monomeric [PhC(NtBu)(2)Si{N(SiMe3)(2)} -> ZnI2]center dot THF (1) and dimeric [{PhC(NtBu)(2)}(N(SiMe3)(2))SiZnI,(mu-I)](2) (2) adducts upon reaction with ZnI2. The formation of 1 and 2 relies upon the solvent used for the reaction or crystallization. When the crystallization is carried out in THF complex 1 is formed, however, when the reaction and crystallization are performed in acetonitrile complex 2 is obtained. Both 1 and 2 were structurally authenticated and the nature of the Si-Zn bond in these complexes was determined by quantum chemical calculations. In addition, a spontaneous inter-conversion between 1 and 2 just by changing the solvents has been also observed; a feature presently not known for silylene-transition metal Lewis adducts.
Keywords: Bis(Silylene ); Carbene Complexes; Crystal -structure Determination; Dative bond; Lewis acid base reaction; Ligands; Main- group compounds; Reactivity; Silicon(II) Bis(Trimethylsilyl)Amide; Carbonyl-Complexes

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Effect of crystal packing on the thermosalient effect of the pincer-type diester naphthalene-2,3-diyl-bis(4-fluorobenzoate): a new class II thermosalient solid - Tamboli, Majid I.; Karothu, Durga Prasad; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Naumov, Pance (Chemistry-A European Journal, 2018)
The pincer-like double ester naphthalene-2,3-diyl-bis(4-fluorobenzoate) (2) is pentamorphic. Upon heating crystals of form I to below their melting point (441-443 K), they undergo a phase transition accompanied by a thermosalient effect, that is, rare and visually striking motility whereby the crystals jump or disintegrate. The phase transition and the thermosalient effect are reversible. Analysis of the crystal structure revealed that form I is a class II thermosalient solid. Crystals of form III also underwent a reversible phase transition in the temperature range of 160 to 170 K; however, they were not thermosalient. Comparison of the structures and the mechanical responses of the two polymorphs revealed that the thermosalient effect of form I was due to reversible closing and opening of the arms of the diester molecules in a tweezer-like action.

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis

Harnessing nucleophilicity of allenol ester with p-quinone methides via gold catalysis: application to the synthesis of diarylmethine-substituted enones - Sharma, Brijesh M.; Rathod, Jayant; Gonnade, Rajesh G.; Kumar, Pradeep (Journal of Organic Chemistry, 2018)
A gold(I)-catalyzed protocol for intermolecular 1,6-conjugate addition of nucleophilic allenol ester generated in situ through [3,3]-sigmatropic rearrangement with p-quinone methides (p-QMs) has been developed. The gold catalyst plays a dual role by the pi-acid-triggered activation of alkynes and at the same time as a Lewis acid for activation of p-QMs toward nucleophilic attack. This method enables rapid access to a wide range of densely functionalized diarylmethine-substituted enones, a Morita-Baylis-Hillman (MBH) product with high selectivity, excellent yields, and broad substrate scope.

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.

Inositol to aromatics -benzene free synthesis of poly oxygenated aromatics - Gurale, Bharat P.; Shashidhar, Mysore S.; Sardessai, Richa S.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
A method for the preparation of benzene derivatives from myo-inositol, an abundantly available phyto chemical is described. 1,3-Bridged acetals of inososes undergo step-wise elimination leading to the formation of polyoxygenated benzene derivatives. This aromatization reaction proceeds through the intermediacy of a beta-alkoxyenone, which could be isolated. This sequence of reactions starting from myoinositol, provides a novel route for the preparation of polyoxygenated benzene derivatives including polyoxygenated biphenyl. This scheme of synthesis demonstrates the potential of myo-inositol as a sustainable non-petrochemical resource for aromatic compounds. (C) 2018 Elsevier Ltd. All rights reserved.

Lithium hydride as an efficient reagent for the preparation of 1,2-anhydro inositols: does the reaction proceed through 'axial rich' conformation? - Sarkar, Nitai; Sardessai, Richa S.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
scyllo-Inositol derived 1,2-trans-diequatorial halohydrins can be efficiently converted to the corresponding epoxides in the presence of lithium hydride. The structure of one of the epoxides was determined by single crystal X-ray diffraction analysis. This provides a potential route for the preparation of ring modified inositol derivatives. DFT calculations suggest that this epoxide formation could be proceeding through the intermediacy of the cyclohexane ring-inverted axial-rich conformer (1,2-trans-diaxial halohydrin). This is supported by the results of DFT calculations on the formation of inositol orthoformate, where the product is locked in the axial-rich conformation, while the starting inositol has the equatorial-rich conformation.

Mechanism of nickel(II)-catalyzed C(2)-H alkynylation of indoles with alkynyl bromide - Khake, Shrikant M.; Jain, Shailja; Patel, Ulhas N.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The nickel system (THF)(2)NiBr2/phen has recently been shown as an efficient catalyst for the C-H bond alkynylation of diverse heteroarenes with (triisopropylsilyl)alkynyl bromide via monodentate chelation assistance. Herein, we report an extensive mechanistic investigation for the direct alkynylation of indoles involving the well-defined nickel catalyst, which features a coordinative insertion pathway of alkynyl bromide with the Ni(II) catalyst. Catalytic relevant nickel complexes, (phen)NiCl2 (5), (phen)(2)NiCl2 (6) and [(phen)(3)Ni].NiCl4 (7) were isolated, and the complexes 6 and 7 were structurally characterized. Well-defined complexes were as competent as the in situ generated catalyst system (THF)(2)NiBr2/phen for the alkynylation of indoles. Various controlled studies and reactivity experiments were performed to understand the probable pathway for the alkynylation reaction. Kinetics analysis highlights that the complex (phen)NiX2 acts as a precatalyst, and the involvement of substrate indole and LiO'Bu are essential for the generation of the active catalyst. Deuterium labeling and kinetic studies suggest that the process involving C-H cleavage and carbo-nickelation of indole is a crucial rate influencing step. Reactivity study of various alkynyl compounds with nickel-species highlights a migratory insertion route for the reaction. DFT calculations firmly support the experimental findings and suggest the coordinative insertion pathway of alkynyl bromide rather than oxidative addition toward the nickel(II) center.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.

Studies on CL-20/HMX (2:1) cocrystal: a new preparation method and structural and thermokinetic analysis - Ghosh, Mrinal; Sikder, Arun K.; Banerjee, Shaibal; Gonnade, Rajesh G. (Crystal Growth & Design, 2018)
A new preparation method for CL-20/HMX (2:1) cocrystal has been established at the laboratory level that is amenable for scale up. Solvent evaporation from a saturated solution of the stoichiometric mixture in the presence of a high boiling antisolvent, comparatively a very efficient and cheaper method, yielded pure cocrystals. Cocrystals were well characterized by spectroscopic, thermoanalytical tools, X-ray diffraction, and microscopic techniques. A correlation of percentage of cocrystal formation with evaporation rate has been obtained through quantitative analysis using Raman spectrometry. An evaporation rate of <1 mL/min consistently produced pure cocrystal confirmed by Raman and powder X-ray diffraction analysis. Thermokinetic analysis suggests the cocrystal to be more stable than CL-20 with an energy of activation of 65 kcal/mol, higher than CL-20 but inferior to HMX. Significant augmentation in the values of k and A over CL-20 justified a faster decomposition rate. Enhanced insensitivity toward friction and impact forces and higher measured velocity of detonation indicate improved performance on incorporation into high explosive formulations.

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.

Synthesis of quinolinyl based pincer copper (II) complexes: an efficient catalyst system for Kumada coupling of alkyl chlorides and bromides with alkyl Grignard reagents - Pandiri, Hanumanprasad; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2018)
Quinolinamide-based pincer copper(ii) complexes, (N),(N),(N)-{C9H6N-(-N)-C(O)CH2NEt2}CuX [((NNN2Et)-N-Q)CuX (X = Cl, 2; X = Br, 3; X = OAc, 4)], were synthesized by the reaction of ligand ((NNN2Et)-N-Q)-H (1) with CuX2 (X = Cl, Br or OAc) in the presence of Et3N. The reaction of ((NNN2Et)-N-Q)-H with CuX (X = Cl, Br or OAc) also afforded the Cu(ii) complexes 2, 3 and 4, respectively, instead of the expected Cu(i) pincer complexes. The formation of Cu(ii) complexes from Cu(i) precursors most likely occurred via the disproportionation reaction of Cu(i) into Cu(0) and Cu(ii). A cationic complex [((NNN2Et)-N-Q)Cu(CH3CN)]OTf (5) was synthesized by the treatment of neutral complex 2 with AgOTf. On the other hand, the reaction of ((NNN2Et)-N-Q)-H (1) with [Cu(MeCN)(4)]ClO4 produced cationic Cu(i) complex, [((NN)-N-Q(H)N-2(Et))Cu(CH3CN)]ClO4 (6), in good yield. All complexes 2-5 were characterized by elemental analysis and HRMS measurements. Furthermore, the molecular structures of 2, 3 and 4 were elucidated by X-ray crystallography. Complex 4 crystallizes in a dimeric and catemeric pattern. The cationic complex 5 was found to be an efficient catalyst for the Kumada coupling reaction of diverse nonactivated alkyl chlorides and bromides with alkyl magnesium chloride under mild reaction conditions.

Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Three-dimensional metal-organic polymer of multivalent hexaphenylbenzene - Madhu, Suresh; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Metal-Organic Frameworks(MOFs) synthesized from ligands more than ten co-ordinating sites may offer material applications due to their structural architecture. Herein, a synthesis of metal-organic framework is reported from a ligand featuring 12-aryl carboxylic acid groups appended on a hexaphenylbenzene and s-block element potassium. The synthesized MOF was characterized by thermogravimetric analysis, infrared spectroscopy and X-diffraction studies. The X-ray crystal structure of MOF was shown to have a significant number of trapped and coordinated water molecules in its three-dimensional framework.

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.

X-ray crystal structures and anti-breast cancer property of 3-tert-butoxycarbonyl-2-arylthiazolidine-4-carboxylic acids - Jagtap, Rohidas M.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Khan, Ayesha A.; Pardeshi, Satish K. (New Journal of Chemistry, 2018)
Diastereomeric `2RS, 4R'-2-arylthiazolidine-4-carboxylic acids (ATCAs) were synthesized and their resolution to chiraly pure N-BOC derivatives was attempted by column chromatography. The absolute stereochemistry of the resolved compounds was ascertained by X-ray single crystal structures. Further application of the synthesized compounds was studied for their in vitro anti-breast cancer activity against MCF7 cell line using DOX as a standard by MTT assay method. Cell morphology analysis was carried out by fluorescence microscopy. The compounds containing `2S' absolute configuration in thiazolidine ring and presence of 2-NO2, 2,6-Cl groups on `2R'-aryl substituent showed significant antibreast cancer activity where some of the compounds were found to be more active than DOX in terms of induced apoptosis mode of MCF7 cell death.

1,6-Conjugate-addition-induced [2+1] annulation of para-quinone methides and pyrazolones: synthesis of bis-spiro compounds with contiguous quaternary spiro-centers - Kale, Someshwar B.; Jori, Popat K.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (Organic Letters, 2019)
A diastereoselective formal 1,6-conjugate-addition-mediated [2 + 1] annulation reaction using p-quinone methides and pyrazolones has been described. The corresponding bis-spiro[cyclohexadienone-cyclopropane-pyrazolone] compounds were obtained in very good yield under mild reaction conditions.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Crystal engineering for intramolecular pi-pi stacking: effect of sequential substitution of f on molecular geometry in conformationally flexible sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Kumar, Deepak; Kotmale, Amol; Gonnade, Rajesh G.; Stuerzer, Tobias (Crystal Growth & Design, 2019)
A small library of ten sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of chronological positioning of the F-atom on the intramolecular pi-stacking assembly. The sequential positioning of F atoms was carried out on one of the aromatic rings that is linked to the sulfonamide moiety directly while the other aromatic ring (phenyl or pyridine) is linked by an ethyl spacer with the sulfonamide moiety. The ethyl spacer is provided to achieve the required flexibility so that both aromatic rings can bend to acquire syn conformation facilitated pi-stacking between electron-deficient and electron-rich aromatic rings. The idea was to study the interplay between hydrogen bonding and pi-stacking synthons in the conformationally flexible sulfonamide derivatives. The solid-state conformation of all the derivatives was investigated using the single-crystal X-ray diffraction technique. Crystal structure analysis revealed that the syn conformation was achieved only in trifluoro and pentafluoro sulfonamide derivatives with benzene substitution while in all other derivatives the molecules take either midway or anti conformations. None of the sulfonamide molecules with a pyridine moiety showed syn conformation. It could be because of the involvement of the pyridine N-atom in the hydrogen bonding dimeric synthon. The molecular conformation study in solution state using 2D NOESY and HOESY NMR experiments also substantiated syn conformation in a pentafluoro sulfonamide molecule with benzene substitution. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed higher stability for the syn conformation over midway and anti orientations.

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure

Efficient broad-band emission from contorted purely corner-shared one dimensional (1D) organic lead halide perovskite - Biswas, Anupam; Bakthavatsalam, Rangarajan; Shaikh, Samir R.; Shinde, Aparna; Lohar, Amruta; Jena, Satyam; Gonnade, Rajesh G.; Kundu, Janardan (Chemistry of Materials, 2019)

Enantioselective formal total synthesis of (-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Organic Letters, 2019)
The enantioselective formal total synthesis of (-)-quinagolide has been accomplished in a linear sequence of 8 purification steps from pyridine. The key steps are (a) organocatalyzed Diets-Alder reaction for fixing all three stereocenters on piperidine ring; (b) protecting group enabled deoxygenation of isoquinuclidine skeleton under Birch reduction condition; (c) Lewis acid (TiCl4) catalyzed intramolecular Friedel-Crafts cyclization of dicarboxylic acid; and (d) one-pot diastereoselective ketone reduction-intramolecular cyclization to form oxazolidinone which enables trans-geometry installation. During the course of the synthesis, an interesting reductive cleavage of the C-N bond in the electron-deficient isoquinuclidine skeleton under the Birch reduction conditions has been observed. This is the first synthetic effort to access the core skeleton of (-)-quinagolide.

Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer

Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.

Neutral imino-methyl benzenesulfonate-ligated Pd(II) complexes and implications in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Mote, Nilesh R.; Manod, M.; Gonnade, Rajesh G.; Chikkali, Samir H. (ACS Omega, 2019)
A reaction between sodium 2-formylbenzenesulfonate and aniline revealed the near-quantitative (91%) formation of sodium-2-((phenylimino)methyl)benzenesulfonate L1. The identity of L1 was unambiguously ascertained using spectroscopic and analytical methods. The scope of this methodology was widened and various electron-donating amines were treated with sodium 2-formylbenzenesulfonate, and a small library of 6 imine ligands L2-L6 was generated. When L2 was treated with [(COD)PdMeCI], instead of the anticipated [L2PdMe(DMSO)] complex, the formation of [(DMSO)(2)Pd2Cl2Me2] Pd Dim was observed. Nevertheless, the desired imino-methyl benzenesulfonate-ligated palladium complex [L2PdMe(Lu)] C1 was obtained by in situ abstraction of chloride and addition of bulky 2,6-lutidine as the donor group. The observation of characteristic Pd-Me protons at 0.06 ppm and the corresponding carbon at -8.1 ppm indicated the formation of C1. These 1D NMR observations were corroborated by 2D C-H correlation spectra and mass analysis, and the existence of C1 was unambiguously ascertained. Along the same lines, L4 and L5 were treated with a palladium precursor to produce [L4/SPdMe(Lu)]-type complexes C2-C3 in 55-84% yield, and their identity was established by using a combination of spectroscopic tools, analytical methods, and single-crystal X-ray diffraction. The synthetic utility of C1-C3 has been demonstrated by utilizing these complexes in the insertion polymerization of ethylene to polyethylene.

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.

Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

TiCl4-n-Bu3N-mediated cascade annulation of ketones with alpha-ketoesters: a facile synthesis of highly substituted fused gamma-alkylidene-butenolides - Palange, Megha N.; Gonnade, Rajesh G.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2019)
A facile protocol for the synthesis of highly substituted fused gamma-alkylidene butenolides using direct annulation of ketones with alpha-ketoesters, which proceeds through TiCl4-n-Bu3N mediated aldol addition followed by an intramolecular enol-lactonization/cyclization cascade, is reported. Diverse 6-5, 7-5 and 8-5 fused bicyclic gamma-ylidene butenolides and highly substituted monocyclic analogs related to biologically relevant natural products were prepared from readily accessible ketone and alpha-ketoester building blocks. The highly step-economic cascade nature, good substrate scope, easy access to complex products with good to excellent yields, gram-scalability, demonstration of synthetic utility, and unambiguous structural confirmation through X-ray crystallography analyses and analogy are the salient features of this work.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

Crystal structure of a 1:1 co-crystal of the anti-cancer drug gefitinib with azelaic acid - George, Christy P.; Sangtani, Ekta; Gonnade, Rajesh G. (Acta Crystallographica Section E: Crystallographic Communications, 2020)
In the title co-crystal, C22H24ClFN4O3·C9H16O4, gefitinib (GTB; systematic name: quinazolin-4-amine) co-crystallizes with azelaic acid (AA; systematic name: nona-nedioic acid). The co-crystal has the monoclinic P21/n centrosymmetric space group, containing one mol-ecule each of GTB and AA in the asymmetric unit. A structure overlay of the GTB mol-ecule in the co-crystal with that of its most stable polymorph revealed a significant difference in the conformation of the morpholine moiety. The significant deviation in the conformation of one of the acidic groups of azelaic acid from its usual linear chain structure could be due to the encapsulation of one acidic group in the pocket formed between the two pincers of GTB namely, the morpholine and phenyl moieties. Both GTB and AA mol-ecules form N-H⋯O, O-H⋯N, C-H⋯O hydrogen bonds with C-H⋯F close contacts along with off-stacked aromatic π-π inter-actions between the GTB mol-ecules.

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose

Drug-drug cocrystals of anticancer drugs erlotinib-furosemide and gefitinib-mefenamic acid for alternative multi-drug treatment - George, Christy P.; Thorat, Shridhar H.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (Crystengcomm, 2020)
Drug-drug cocrystals of anticancer drugs erlotinib and gefitinib with furosemide and mefenamic acid, respectively, have been synthesized. The 1:1 erlotinib-furosemide cocrystal crystallizes in the monoclinic centrosymmetric P2(1)/n space group containing one molecule of each component in the asymmetric unit. In contrast the 1:1 gefitinib-mefenamic acid cocrystal hydrate belongs to the monoclinic centrosymmetric P2(1)/c space group comprising one molecule of both drugs along with one water molecule in the asymmetric unit. The solubility and dissolution rate study revealed higher solubility for BCS class II drugs, furosemide, and mefenamic acid, while the solubility and dissolution rate of erlotinib showed a significant reduction in the cocrystal salt. Conversely, the solubility of gefitinib didn't reveal a substantial decrease; however, the dissolution rate has been reduced in the cocrystal hydrate. Further, an attempt has been made to correlate the crystal structures of the erlotinib-furosemide and gefitinib-mefenamic acid cocrystals with their solubilities and dissolution rate.

Effect of substituent of roof shape amines on the molecular recognition of optically active acids by NMR spectroscopy - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (ChemistrySelect, 2020)
Optically active roof shape derivatives of benzyl amines were synthesized and screened as chiral solvating agents for the study of molecular recognition of chiral compounds by NMR and UV spectroscopy. The effect of substituents on the aromatic ring of benzyl unit is investigated to assess the binding ability with the analyte and an experimental correlation is observed. Altering the substituents on the ring of benzyl amine and the acidic substrates, significantly influence the CSA interactions. The supramolecular interactions between acid and amine in the single crystal X-ray analysis of the diastereomeric salts provide further insight of the mode of molecular recognition.
Keywords: Chiral Solvating Agents; molecular recognition; NMR spectroscopy; Roof Shape Amine; UV spectroscopy

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Furan-derived chiral bicycloaziridino lactone synthon: collective syntheses of oseltamivir phosphate (Tamiflu), (S)-pipecolic acid and its 3-hydroxy derivatives - Chavan, Subhash P.; Kadam, Appasaheb L.; Shinde, Shrikrishna S.; Gonnade, Rajesh G. (Chemistry-An Asian Journal, 2020)
A unified synthetic strategy for oseltamivir phosphate (tamiflu), (S)-pipecolic acid, and its 3-hydroxy derivatives from furan derived common chiral bicycloaziridino lactone synthon is described here. Key features are the short (4-steps), enantiopure, and decagram-scale synthesis of common chiral synthon from furan and its first-ever application in the total synthesis of biologically active compounds by taking the advantages of high functionalization ability of chiral synthon.
Keywords: Aziridine synthon; Chiral auxiliary; collective synthesis; Pipecolic acid; Tamiflu

Influence of fluorine substitution on the molecular conformation of 3 `-deoxy-3 `-fluoro-5-methyluriaine - Aher, Manisha N.; Erande, Namrata D.; Kumar, Vaijayanti A.; Fernandes, Moneesha; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2020)
{Fluorine substitutions on the furanose ring of nucleosides are known to strongly influence the conformational properties of oligonucleotides. In order to assess the effect of fluorine on the conformation of 3'-deoxy-3'-fluoro-5-methyluridine (T-R(F)), C-10 H13FN2O5, we studied its stereochemistry in the crystalline state using X-ray crystallography. The compound crystallizes in the chiral orthorhombic space group P2(1)2(1)2(1) and contains two symmetry-independent molecules (A and B) in the asymmetric unit. The furanose ring in molecules A and B adopts conformations between envelope (E-2, 2'-endo
Keywords: crystal structure; fluoro nucleoside; pseudorotation parameter; sugar puckering; uridine

Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.

Para-selective copper-catalyzed C(sp(2))-H amidation/dimerization of anilides via a radical pathway - Viveki, Amol B.; Garad, Dnyaneshwar N.; Gonnade, Rajesh G.; Mhaske, Santosh B. (Chemical Communications, 2020)
Copper-catalyzed amidation/dimerization of anilides via regioselective C(sp(2))-H functionalization is achieved. The para-selective amidation is accomplished on the anilide aromatic ring via a radical pathway leading to C-N bond formation in the presence of ammonium persulfate as a radical source/oxidant for the copper catalyst. The developed protocol tolerates a wide range of anilide substrates. The regioselectivity is confirmed by single-crystal X-ray studies.

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions

Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Synthesis, crystal structure and Hirshfeld surface analysis of the hydrated form of N’, N-(1,4-phenylenebis(methanylylidene) di(iso-nicotinic hydrazide) - Ingle, Kapil S.; Mohurle, Smital A.; Bairagi, Keshab M.; Shaikh, Tabrez R.; Venugopala, Katharigatta N.; Chandrashekharappa, Sandeep; Gonnade, Rajesh G.; Nayak, Susanta K. (Chemical Data Collections, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The title compound, C<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">20<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">16<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">6<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was synthesized by reflux with isonicotinic hydrazide and terephthaldehyde in ethanol solvent with the acidic condition. The single-crystal X-ray structure determination of the title compound, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N, N<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-(1,4-phenylene bis (methanylylidene) di(iso-nicotinic hydrazide), reveals that the molecule crystallizes in center of symmetry with water molecules (Dihydrated form, C<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">20<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">16<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">N<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">6<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">.2H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O) through N-H∙∙∙O and C-H∙∙∙O hydrogen bondings. Further, the crystal structure is stabilized by O-H∙∙∙O and weak C-H∙∙∙N hydrogen bondings with the formation of infinite chain and dimer. Further, surface analysis and fingerprint plot reveal that the significant hydrogen bonding such as H•••O (15.9%) and N•••H (11.4%) interactions play the most crucial role for its molecular packing.

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Access to a variety of Ge(II) and Sn(II) compounds through substitution of hypersilyl moiety - Bisai, Milan Kumar; Ajithkumar, V. S.; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
We have prepared amidinato-germylene (3) and -stannylene (4) with a tris(trimethylsilyl)silyl substituent and subsequently substituted the hypersilyl moiety by reacting 3 with chlorophosphines, which led to phosphino germylenes (5 and 6) with concomitant liberation of (Me3Si)(3)SiCl. Exploiting the fluoride affinity of the silicon atom, we have prepared pentafluoropyridyl germylene (7) and -stannylene (8) by reacting 3 and 4 with C5F5N with simultaneous elimination of (Me3Si)(3)SiF. These are the first examples of aryl germylenes or stannylenes prepared via C-F bond activation of a perfluoroarene. The reaction of 4 with Me3NO resulted in a novel Sn2O2 ring (9). All compounds were characterized by single-crystal X-ray structure determination studies.

Access to enantiomeric organic compounds with potential for synthesis via racemic conglomerates: inositol derivatives as a case in point - Patil, Nivedita T.; Patil, Madhuri T.; Sarkar, Nitai; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2021)
The crystal structure database was used to identify inositol derivatives that could be crystallizing as racemic conglomerates. Among the six racemic inositol derivatives identified, racemic 4-O-tosyl-6-O-benzyl-myo-inositol-1,3,5-orthoformate (A) was found to be a true conglomerate and was resolved on the multigram scale by the preferential crystallization technique. This resolution procedure does not require the use of any enantiomeric resolving agent. The resolved enantiomers of A are useful for the synthesis of natural and unnatural enantiomeric derivatives of inositol, since they carry orthogonal hydroxy protecting groups. Racemic 4-O-methanesulfonyl-myo-inositol-1,3,5-orthoformate (B) on crystallization from common organic solvents generally yielded racemic twin crystals, while in the presence of structural analogs as additives, they yielded true racemic crystals. A comparison of the crystal structures of the true racemate, twinned crystal and crystal of one of the enantiomers of B, revealed the reasons for the formation of polymorphic (twin) crystals. Such instances are relatively rarely encountered but nevertheless shed light on our understanding of polymorphism and twinning of crystals.

Achiral and chiral NNN-pincer nickel complexes with oxazolinyl backbones: application in transfer hydrogenation of ketones - Jagtap, Rahul A.; Ankade, Shidheshwar B.; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2021)
We describe the synthesis of new NNN-oxazolinyl-pincer nickel complexes and their application in the transfer hydrogenation of ketones. Achiral NNN-ligands, R `(2)-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [((R ` 2-OxNNNEt2))-H; R' = H (3a), R ` = Me (3b)], and chiral ligands, (R)-R `-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [(R)-((R `-OxNNNEt2))-H; R ` = Ph (3c), R ` = CH2Ph (3d), R ` = Pr-i (3e), R ` = (CH2Pr)-Pr-i (3f)], were efficiently synthesized. Treatment of these ligands with (DME)NiCl2 afforded the desired amido-pincer nickel complexes, ((R ` 2-OxNNNEt2))NiCl [R ` = H (4a), R ` = Me (4b)] and ((R `-OxNNNEt2))NiCl [R ` = Ph (4c), R ` = CH2Ph (4d), R ` = Pr-i (4e), R ` = (CH2Pr)-Pr-i (4f)], in good yields. All the ligand precursors and nickel complexes were thoroughly characterized by various analytical techniques. The molecular structures of 4a, 4d and 4f were established by X-ray crystallography. The developed nickel complexes were found to be efficient catalysts for the transfer hydrogenation of ketones using (PrOH)-Pr-i as a viable hydrogen source. Enantioselectivity in hydrogenation was not observed with the developed chiral catalysts.

Acid mediated sulfonylation of para-quinone methides with tosylmethyl isocyanides for the synthesis of diarylmethyl sulfones - Kumar, Pawan; Kale, Someshwar B.; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2021)
An efficient, hydrochloric acid promoted reaction for the synthesis of diarylmethyl sulfones has been developed via unprecedented 1, 6-conjugate addition reaction of tosylmethyl isocyanide (TosMIC) with para-quinone methides.This catalyst free reaction provides various diarylmethyl sulfones in good to excellent yields in an operationally simple method under metal free conditions. Further transformations of the productsare also demonstrated.
Keywords: 1; 6-Conjugate addition; aromatization; Diarylmethylsulfone; para-Quinonemethide; TosMIC

Chemistry, anti-diabetic activity and structural analysis of substituted dihydropyrimidine analogues - Bairagi, Keshab M.; Younis, Nancy Safwat; Emeka, Promise Madu; Venugopala, Katharigatta N.; Alwassil, I, Osama; Khalil, Hany Ezzat; Sangtani, Ekta; Gonnade, Rajesh G.; Mohanlall, Viresh; Nayak, Susanta K. (Journal of Molecular Structure, 2021)
In an effort to identify an anti-diabetic agent, a series of methyl/ethyl 4-(hydroxyphenyl)-6-methyl-2-oxo/thioxo-1,2,3,4 tetrahydropyrimidine-5-carboxylate analogues (4a-h) have been synthesized, purified, and characterized by using Fourier-Transform Infrared Spectroscopy (FT-IR) and NMR (H-1 and C-13). The synthesized compounds were screened for anti-hyperglycemic activity using Streptozotocin (STZ) induced diabetic rat model. The anti-hyperglycemic activity of dihydropyrimidine (DHPM) compound is mainly analyzed with the variation of substituents present on the phenyl ring and urea/thiourea group on pharmacophoric features. Further, the crystal structure and supramolecular characteristics of two compounds 4c and 4f were analyzed through a single-crystal X-ray method and the Hirshfeld Surface Analysis, which shows hydrogen bonding through N-H center dot center dot center dot O and N-H center dot center dot center dot S interactions with the formation of ring motif in the crystal structure. It is interesting to note that among the title compounds, the 4a, 4e, 4f, and 4g significantly displayed a better hypoglycemic effect in vivo rat model study. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dihydropyrimidine (DHPM); Hypoglycemia; Streptozotocin (STZ); Type-2 diabetes mellitus (T2DM)

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction

Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).

Divergent approach to the synthesis of (-)-balanol heterocycle and cis-3-hydroxypipecolic acid based on chiral 2-aminoalkanol equivalent - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron, 2021)
Enantioselective synthesis of the hexahydroazepine core of (-)-balanol and formal synthesis of cis-3hydroxypipecolic acid from a common intermediate have been accomplished by a divergent path. The common intermediate was accessed from a favorably protected enantiomerically pure 2-amino-1,3,4-butanetriol (ABT) equivalent via oxidation and Wittig olefination. The synthesis of (-)-balanol heterocycle featured tandem reduction/acetal-deprotection/gamma-lactonization reaction and a one-pot azide reduction followed by seven membered aza-heterocycle formation while the route to cis-3-hydroxypipecolic acid highlighted the base induced piperidine ring formation and regioselective benzylidine-acetal cleavage. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Amino-alcohol; desymmetrization; Hexahydroazepine; Piperidine alkaloids; Protein kinase

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

Formal synthesis of (-)-quinagolide: diastereoselective ring expansion via a bicyclic aziridinium ion strategy to access the octahydrobenzo[g]quinoline architecture - Chavan, Subhash P.; Kawale, Sanket A.; Pisal, Mahesh M.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2021)
The diastereoselective formal synthesis of (-)-quinagolide, a D-2 receptor agonist, has been achieved. The synthesis started from L-pyroglutamic acid and relied on utilization of (a) a stereospecific catalytic hydrogenation and diastereoselective Horner-Emmons-Michael cascade to obtain functionalized prolinate, (b) a Lewis acid mediated Pummerer cyclization to construct a tricyclic fused ring system, and (c) a diastereoselective ring expansion via a bicyclic aziridinium intermediate to access the required 3-substituted piperidine scaffold.

Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.

Metal halide structure and the extent of distortion control the photo-physical properties of luminescent zero dimensional organic-antimony(iii) halide hybrids - Biswas, Anupam; Bakthavatsalam, Rangarajan; Mali, Bhupendra P.; Bahadur, Vir; Biswas, Chinmoy; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Antimony(iii) halide based zero dimensional hybrids have gained attention as broadband emitters. Until now, quadrangular pyramidal SbX5 based and octahedral SbX6 based 0D hybrids have been reported utilizing different organic ligands demonstrating some structural tunability affecting their emissive properties. Utilizing a common organic ligand, here we demonstrate the structural tunability (quadrangular pyramidal, octahedral, or a combination thereof) of the metal halide unit in Sb(iii)Cl 0D hybrids with contrasting photo-physical properties (broadband, Stokes shift, strong/weak colored emission). The structure-property-mechanism correlation of the synthesized compounds [1 (C12H52Cl18N8O4Sb3; tris Sb green); 2 (C12H50Cl14N8O3Sb2; tris Sb red); 3 (C24H88Cl25N16O4Sb3; tris Sb yellow)] identifies crucial factors that control their emissive properties. The X-ray analysis reveals the structure (1-octahedral; 2-quadrangular pyramidal; 3-combination thereof) and the order of the extent of structural distortion as 1-3 MUCH LESS-THAN 2. The metal halide coordination environment asymmetry and its structure are observed to dictate PL emission energy (1-green; 2-red; 3-yellow) as supported by a qualitative Molecular Orbital scheme. The extent of structural distortion guides the observed Stokes shifts (1-165 nm; 2-290 nm; 3-200 nm; 1-3 < 2). Interestingly, the extent of distortion is found to be well correlated with the observed PLQY (1-45%; 2-6%; 3-43%; 1-3 >> 2). This report clearly demonstrates the structural tunability and the effect of the metal halide unit structure/distortion in shaping the emissive properties of 0D organic Sb(iii) halide hybrids.

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Polymorphs and hydrates of the anticancer drug erlotinib: X-ray crystallography, phase transition and biopharmaceutical studies - Thorat, Shridhar H.; George, Christy P.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (CrystEngComm, 2021)
Erlotinib, a non-small cell lung cancer BCS class II drug, was found to occur as two polymorphs and two hydrates depending on the crystallization conditions. The monohydrate (form III), which has been reported in patents and publications, is the preferred crystalline phase from solution crystallization. The other forms (polymorphs, forms I and II, and a trihydrate, form IV) are solvent and condition-specific. Form I was exclusively and reproducibly obtained from dried non-polar solvents (viz. toluene, benzene, and xylene) using a solution crystallization method under controlled conditions. In contrast, form II was obtained by the rotary evaporation technique under reduced pressure from polar solvents (viz. dichloromethane, ethyl acetate, acetone, and acetonitrile). Slow evaporation from polar and non-polar solvents under open conditions yielded form III crystals, whereas evaporation from acetone-acetonitrile-water mixtures yielded form IV crystals. DSC and variable temperature PXRD studies revealed form I to be the most stable phase while the other solid forms displayed thermally induced polymorphic transitions into form I crystals. Further, form I and form III are found to be stable over the 30-90% RH range. Further, form I displayed solution-mediated transformation into form III (monohydrate) when left to stand in the mother liquor for a longer duration (1-2 days). Similarly, the unstable form IV crystals transformed into the stable form III crystals within 1-2 h when exposed to an open atmosphere. Fast crystallization from polar solvents using the rotary evaporation technique enabled us to capture the metastable polymorph, form II. Early separation of form I from its mother liquor prevented its solution-mediated transformation into the monohydrate, form III. The water activity study revealed that form III is the most preferred solid phase in the presence of water. Dissolution rate measurements showed that the rate of form II is almost comparable to that of the marketed erlotinib hydrochloride. In contrast, for the other forms, the dissolution profiles showed a considerable decrease. Although the crystal structures of form I and form III have been published previously, this manuscript gives a comprehensive overview of the free base solid forms of erlotinib, the phase transitions amongst them and their biopharmaceutical properties.

Reactivities of silaimines with boranes: from cooperative B-H bond activation to donor stabilized silyl cation - Bisai, Milan Kumar; Sharma, Vishal; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
The recently published silylene with a tris(trimethylsilyl) group, PhC(NtBu)(2)SiSi(SiMe3)(3) (1), was reacted with the organic azides such as SiMe3N3 and AdN(3) to form the respective hypersilylsilaimines, PhC(NtBu)(2)Si(=NR)Si(SiMe3)(3) 2 (R = SiMe3) and 3 (R = Ad). The B-H bond of HBpin or HBcat was split across the Si=N bond upon reaction with 2, which generated 4 and 5, respectively. However, we could not obtain the crystals of 4 and 5 appropriate for X-ray diffraction. Subsequently, we performed the analogous reactions with a related silaimine PhC(NtBu)(2)Si(=NSiMe3)N(SiMe3) 2 (2') and isolated similar B-H bond activated products 6 and 7. The reaction of 2' with HBCl2 resulted in donor stabilized silyl cations (8 and 9) supported by an amidinate ligand.

Stabilization of the elusive antimony(I) cation and its coordination complexes with transition metals - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Angewandte Chemie-International Edition, 2021)
Upon stabilization by 5,6-bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two-electron oxidation of the ligand to form a P-P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb-I site in 1 was found to bind to metal centers, forming complexes with Au-I, Ag-I and Cu-I. Compound 1 reduced Cu-II to Cu-I and formed a coordination complex with the resulting Cu-I species. The effects of the electron-rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies.
Keywords: antimony(I) cation; coordination modes; nucleophilicity; phosphine ligands; reduction

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.

Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.

Monomeric magnesium catalyzed alkene and alkyne hydroboration - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2022)
In this work, two monomeric magnesium alkyl complexes (1 and 2) were prepared using bis(phosphino)carbazole framework and among them 1 has been used as a catalyst for hydroboration of alkenes and alkynes with pinacolborane (HBpin). A broad variety of aromatic and aliphatic alkenes and alkynes were efficiently reduced. Anti-Markovnikov regioselective hydroboration of alkenes and alkynes was achieved, which was confirmed by deuterium-labelling experiments. The work represents the first example of the use of magnesium in homogeneous catalytic hydroboration of alkene with broad substrate scope. Experimental mechanistic investigations and DFT calculations provided insights into the reaction mechanism. Finally, the hydroboration protocol was extended to terpenes.
Keywords: carbazole; Magnesium; monomeric complexes; phosphorous; X-ray Structure

Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Rapid synthesis of the epi-biotin sulfone via tandem S,N-carbonyl migration/aza-michael/spirocyclization and haller-bauer reaction - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (ACS Omega, 2022)
A synthesis of 2-epi-biotin sulfone was accomplished from commercially available L-cysteine. The synthesis features an unprecedented tandem S,N-carbonyl migration/aza-Michael/spirocyclization reaction from an L-cysteine-derived enone with aq. ammonia, in which three new sigma bonds and two rings are formed. In addition, the synthesis includes a highly diastereoselective late-stage Haller-Bauer reaction of sulfone for direct introduction of the carbon side chain.

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Room temperature Z-selective hydrogenation of alkynes by hemilabile and non-innocent (NNN)Co(ii) catalysts - Sharma, Dipesh M.; Gouda, Chandrakant; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2022)
Hemilabile and phosphine-free quinolinyl-based NNN-type pincer and non-pincer cobalt complexes were developed for the room temperature catalytic transfer semi-hydrogenation of alkynes to Z-alkenes. Treatment of the quinolinyl-amine ligand, [C9H6N(NH)CH2CH2NEt2] ((NNN2NEt2)-N-Q-N-CH)-H with CoX2 afforded the pincer complexes kappa(3)-((NNN2NEt2)-N-Q-N-CH)CoX2 (X = Cl, Br), whereas, the quinolinyl-amide ligand, [C9H6N(NH)C(O)CH2NEt2] ((NNNNEt2)-N-Q-N-C(O))-H gave chelate anionic complexes kappa(2)-((NN)-N-Q)CoX2((NHNEt2)-H-C(O)) (X = Cl, Br). The well-defined anionic non-pincer cobalt complexes efficiently catalyzed the semi-hydrogenation of diverse alkynes to deliver highly chemoselective and stereodivergent Z-alkenes at room temperature. This hydrogenation exhibited broad substrate scope with the tolerance of sensitive functional groups, such as -Cl, -Br, -I, -OH, -NH2, -COOMe, and pyridinyl, employing a stable and user-friendly ammonia borane hydrogen source.

Synthesis, crystal structure and Hirshfeld surface analysis of a zinc(II) coordination polymer of 5-phenyl-1,3,4-oxadiazole-2-thiolate - Pirimova, Mehribon; Torambetov, Batirbay; Kadirova, Shakhnoza; Ziyaev, Abdukhakim; Gonnade, Rajesh G.; Ashurov, Jamshid (Acta Crystallographica Section E Crystallographic Communications, 2022)
A new zinc coordination polymer with 5-phenyl-1,3,4-oxadiazole-2-thiolate, namely, catena-poly[zinc(II)-bis(μ2-5-phenyl-1,3,4-oxadiazole-2-thiolato)-κ2N3:S;κ2S:N3], [Zn(C8H5N2OS)2]n, was synthesized. The single-crystal X-ray <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/D01712.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">diffraction analysis shows that the polymeric structure crystallizes in the centrosymmetric monoclinic C2/c <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group. The ZnII atom is coordinated to two S and two N atoms from four crystallographically independent (L) ligands, forming zigzag chains along the [001] direction. This polymer complex forms an eight-membered [Zn–S–C–N–Zn–S–C–N] chair-like ring with two ZnII atoms and two ligand molecules. On the Hirshfeld surface, the largest contributions come from the short contacts such as <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces, including H⋯H, C⋯H and S⋯H. Interactions including N⋯H, O⋯H and C⋯C contacts were also observed; however, their contribution to the overall stability of the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Lattice" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal lattice is minor.
Keywords: 3; 4-oxadiazole-2-thiol; coordination polymer; Hirshfeld surface analysis; crystal structure; zinc complex; 5-phenyl-1

Tailoring diradicaloid properties of expanded isophlorinoids with systematic core-modification - Ambhore, Madan D.; Shukla, Pragati; Gonnade, Rajesh G.; Anand, Venkataramanarao G. (Chemical Communications, 2022)
Herein, we describe the synthesis, structural diversity and diradicaloid characteristics of 38 pi core-modified aromatic expanded isophlorins with eight heterocyclic rings. The diradicaloid character of expanded isophlorinoid macrocycles was engineered by systematic structural modification. Depending on the nature of the link between the heteroatoms, they adopt planar and non-planar conformations. This large structural variation with a significant difference in the extent of aromaticity is correlated with the magnitude of their respective diradical character.

Accelerated Rauhut-Currier dimerization enabled the synthesis of (+/-)-incarvilleatone and anticancer studies - Kotammagari, Tharun K.; Misra, Sweta; Paul, Sayantan; Kunte, Sunita; Gonnade, Rajesh G.; Santra, Manas K.; Bhattacharya, Asish K. (Beilstein Journal of Organic Chemistry, 2023)
The total synthesis of racemic incarvilleatone has been achieved by utilizing unexplored accelerated Rauhut-Currier (RC) dimeriza-tion. The other key steps of the synthesis are oxa-Michael and aldol reactions in a tandem sequence. Racemic incarvilleatone was separated by chiral HPLC and the configuration of each enantiomer was determined by single-crystal X-ray analysis. In addition, a one-pot synthesis of (+/-)-incarviditone has been achieved from rac-rengyolone by using KHMDS as a base. We have also assessed the anticancer activity of all the synthesized compounds in breast cancer cells nonetheless, they exhibited very limited growth suppression activity.
Keywords: dimerization; incarviditone; incarvilleatone; oxa-Michael; Rauhut-Currier

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Intramolecular donor-stabilized tetra-coordinated germanium(iv) di-cations and their Lewis acidic properties - Peddi, Balakrishna; Khan, Souvik; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Chemical Science, 2023)
We report the first examples of intramolecular phosphine-stabilized tetra-coordinated germanium(iv) di-cationic compounds: [(L2Ge)-Ge-iPr][CF3SO3](2)3iPr and [(L2Ge)-Ge-Ph][CF3SO3](2)3Ph (L-iPr = 6-(diisopropylphosphanyl)-1,2-dihydroacenaphthylene-5-ide; L-Ph = 6-(diphenylphosphanyl)-1,2-dihydroacenaphthylene-5-ide). The step wise synthetic strategy involves the isolation of neutral and mono-cationic Ge(iv) precursors: [(L2GeCl)-Ge-iPr][X] (X = GeCl(3)1iPr, OTf 2iPr), [(L2GeCl2)-Ge-Ph] 1Ph and [(L2GeCl)-Ge-Ph][OTf] 2Ph. Both 3iPr and 3Ph exhibit constrained spiro-geometry. DFT studies reveal the dispersion of di-cationic charges over P-Ge-P sites. Anion or Lewis base binding occurs at the Ge site resulting in relaxed distorted trigonal bipyramidal/tetrahedral geometry. 3iPr and 3Ph activate the Si-H bond initially at the P-site. The hydride ultimately migrates to the Ge-site rapidly giving [(L2GeH)-Ge-Ph][CF3SO3] 3PhH, while sluggishly forming [(L2GeH)-Ge-iPr][CF3SO3] 3iPrH. Compounds 3iPr and 3Ph were tested as catalysts for the hydrosilylation of aromatic aldehydes. While catalytic hydrosilylation proceeded via the initial Et3Si-H bond activation in the case of 3iPr, compound 3Ph as a catalyst showed a masked Frustrated Lewis Pair (FLP) type reactivity in the catalytic cycle.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

NHC-catalyzed enantioselective synthesis of tetracyclic δ-lactones by (4+2) annulation of ortho-quinodimethanes with activated ketones - Sarkar, Deeptanu; Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2023)
The N-heterocyclic carbene (NHC)-catalyzed generation of ortho-quinodimethanes (o-QDMs) from 9H-fluorene-1-carbaldehydes followed by the interception with activated ketones resulting in the enantioselective synthesis of tetracyclic delta-lactones is presented. High diastereoselectivity of products, remote C-(sp(3))-H functionalization, broad substrate scope, and mild reaction conditions are the notable features of the present (4 + 2) annulation.

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis

Organocatalysed one-pot three component synthesis of 3,3′-disubstituted oxindoles featuring an all-carbon quaternary center and [spiro 2H-pyran-3,4′-indoline] - Nichinde, Chandrakant B.; Patil, Baliram R.; Chaudhari, Suryakant S.; Mali, Bhupendra P.; Gonnade, Rajesh G.; Kinage, Anil K. (RSC Advances, 2023)
A simple and efficient methodology for the one-pot synthesis of 3,3 `-disubstituted oxindoles featuring an all-carbon quaternary center has been demonstrated through l-proline catalysed three-component reaction based on sequential Knoevenagel condensation/Michael addition and also one-pot synthesis of spiro[2H-pyran-3,4 `-indoline] through consecutive Knoevenagel condensation/Michael addition/reduction/cyclization reactions from readily available isatin derivatives, malononitrile, and ketones. The present methodology presents several advantages, including simple reaction set-up, short reaction times, and easy to work-up. Also, this strategy offers broad substrate scope with excellent yields and high atom economy, under mild reaction conditions.

Palladium-catalyzed chemoselective oxygenation of C(sp2)-H and C(sp3)-H bonds in isatins - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Organic Letters, 2023)
The palladium-catalyzed chemoselective C(sp2)-H and C(sp3)-H bond oxygenation of substituted isatin derivatives is reported. This mild protocol exhibits the C5 C(sp2)-H oxygenation of isatins through electrophilic intermolecular C-H palladation in concentrated solutions using PhI(OAc)2 or Selectfluor as an oxidant, whereas it exhibits- N-CH3 C(sp3)-H oxygenation in dilute solutions via carbonyl-assisted intramolecular palladation in the presence of K2S2O8. This oxygenation reaction provides a direct and unified approach for synthesizing diverse oxygenated isatins with sensitive functionalities, including biorelevant compounds.

Palladium-catalyzed polar solvent empowered synthesis of hyper-branched ethylene oligomers and their applications - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Pol, Harshawardhan V.; Prabhu, M. Basava; Rokade, Dhammaraj; Nandimath, Sheetal; Chikkali, Samir H. (Polymer Chemistry, 2023)
In this contribution, we report the synthesis of two naphthoxy imine ligands, 2-(((2,6-dibenzhydryl-4-methoxyphenyl)imino)methyl)naphthalen-1-ol (L1) and 2-(((2,6-diisopropylphenyl)imino)methyl)naphthalen-1-ol (L2), with different steric and electronic features. L1 and L2 were treated with [(TMEDA)PdMe2] to obtain the corresponding neutral palladium(ii) complexes Cat.1 and Cat.2 in excellent yields. The identity of Cat.1 and Cat.2 was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. When exposed to 5 bar ethylene pressure, Cat.1 produced hyperbranched ethylene oligomers. The microstructure analysis of ethylene oligomers confirmed the existence of methyl, ethyl, propyl, and sec-butyl branches, with a molecular weight (M-n) of 500-1400 g mol(-1), a PDI of 1.46-2.10, and 67-106 branches per 1000 carbon atoms. The use of a polar solvent, tetrahydrofuran, led to a remarkable 3-fold increase in oligomerization activity without compromising the branching and molecular weight. The resultant hyperbranched ethylene oligomers were selectively monofunctionalized using industrially practiced hydroformylation, ozonolysis, and epoxidation, almost quantitatively. The hydroxy functionalized ethylene oligomer (F4) (5 wt%) was melt-compounded with LLDPE and Nylon-6 to produce a tough yet flexible blend with a higher strain-to-failure as compared to an uncompatibilized blend.

Polymorph II of hydroxyurea 150 years after its first synthesis - Rai, Sunil K.; Tothadi, Srinu; Arhangelskis, Mihails; George, Christy P.; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2023)
A new polymorph of hydroxyurea (HU) was crystallized 150 years after its first synthesis. Due to its medicinal use in neoplastic diseases and sickle cell anemia, a high throughput screen of HU binary cocrystals was attempted. Instead of a cocrystal, an isoenergetic form II crystallized concomitantly with urea in methanol.

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).

Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine

Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Zwitterionic disilanylium from an unsymmetrical disilene - Bisai, Milan Kumar; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The reaction of PhC(NtBu)2SiSi(SiMe3)(3) (1) with Me3SiCH(2)Cl afforded an unsymmetrical sp(2)-sp(3) disilene, 2, with concomitant elimination of Me3SiCl. The analogous reaction with PhC(NtBu)2SiCl resulted in the oxidative addition of the C-Cl bond at the Si(II) atom (3). The reactions of 2 with sulfur and selenium led to compounds with Si=E (E=S (4) and Se (5)) double bonds. Tellurium reacted differently with 2 and furnished a zwitterionic compound, 6.

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene

1,6-Conjugate addition of in situ generated aryldiazenes to p-quinone methides - Mamale, Ajay G.; Paul, Sayantan; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2024)
Herein we report a transition-metal free, base-mediated 1,6-conjugate addition of aryldiazenes to para-quinone methides (p-QMs). Arylhydrazines were used for the in situ generation of aryldiazenes using a base-mediated protocol in the presence of air as the oxidant. The 1,6-conjugate addition of aryldiazenes to para-quinone methides via a radical mechanism is followed by an oxidative rearrangement to furnish the desired product, arylhydrazones. Interestingly, our synthetic protocol results in the formation of an aryldiazene radical, which undergoes 1,6-conjugate addition with p-QMs to furnish the arylhydrazones.

Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product

Catalytic cycloisomerization-oxidative cyclization reaction sequence of enyne diesters derived from 2-propargyloxyarylaldehydes - Prajapati, Karmdeo; Saini, Manoj Kumar; Gonnade, Rajesh G.; Basak, Ashok K. (Organic Letters, 2024)
Enyne diesters derived from 2-propargyloxyarylaldehydes are converted into 2-oxopyranochromenes via In(OTf)3-catalyzed cycloisomerization and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-mediated oxidative cyclization reaction sequence in one pot. The process possesses broad substrate scope and good functional group compatibility and generates various 4-(hetero)aryl-substituted 2-oxopyranochromenes in 32-79% yields (over two steps). 2-Oxopyranochromenes undergo selective decarboxylation under Krapcho conditions. When treated with aliphatic secondary amines in DMF, 2-oxopyranochromenes undergo decarboxylative amination at ambient temperature to generate 2-amino-substituted functionalized chromenes in good yields.

Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter

Manganese-catalyzed chemoselective direct hydrogenation of α,β-epoxy ketones and α-ketoamides at room temperature - Shabade, Anand B.; Singh, Rahul K.; Gonnade, Rajesh G.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
Chemoselective hydrogenation of alpha,beta-epoxy ketones and alpha-ketoamides is achieved at room temperature (25 degrees C) using 2.0 bar H-2 and a pincer-ligated Mn(I) catalyst that provides synthetically valuable alpha-hydroxy epoxides and alpha-hydroxy amides. This protocol applies to a wide range of alkyl- and aryl-substituted alpha,beta-epoxy ketones, including terpenes (alpha-ionone, nootkatone, and R-carvone)- and steroids (testosterone and progesterone)-derived epoxy ketones, and tolerates H-2 sensitive functionalities, such as halides, acetyl, nitrile, nitro, epoxide, alkenyl and alkynyl groups. Additionally, alpha-ketoamides bearing reducible functional groups, including acetyl and diazo benzene, were untouched under this protocol and selectively converted to alpha-hydroxy amides. A preliminary mechanistic study highlighted the metal-ligand cooperative H-2 activation process.
Keywords: alpha; beta-epoxy ketones; chemoselectivity; direct hydrogenation; manganese; Metal-ligand cooperation

Methanesulfonic acid-catalyzed friedel-crafts alkylation: towards sustainable synthesis of arylalkanes from donor-acceptor cyclopropane ketones - Goswami, Lakshmi; Paul, Sayantan; Mamale, Ajay G.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2024)
We present herein Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane ketones. The presence of the 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules inspired us to pursue the direct synthesis of these structural frameworks. Utilizing methanesulfonic acid (MeSO3H) as a catalyst, we achieved a more environmentally friendly and high-yielding synthesis, owing to its cost-effectiveness, biodegradability, transition-metal and additives free conditions. Furthermore, we have successfully extended our developed methodology to thiophenols, resulting in the production of sulfur-based butan-1-one derivatives in good yields. The presence of 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules prompted us to develop a Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane. image
Keywords: donor-acceptor cyclopropane; Friedel-Crafts alkylation; methanesulfonic acid; Phenols; thiophenol

Pyridazine-Based Aggregation Induced Emission Active Conjugates: Synthesis, Single Crystal XRD Analysis, and Self-Assembly Assessment - Waghchoure, Aishwarya P.; Sangale, Vijay B.; Shaligram, Parth S.; Lambud, Sushil; Pardeshi, Satish K.; Gonnade, Rajesh G.; Bandaru, Sateesh; More, Sandeep; Reddy, J. Prakasha; Bhosale, Rajesh S. (CHEMISTRYSELECT, 2024)
Keywords: AIE; Pyridazine; Self-assembly; Single crystal

Regio- and stereoselective construction of 1,3,5-triaroylcyclohexanes via KO t Bu-mediated cyclotrimerization of aryl vinyl ketones - Mahale, Sachin D.; Yadav, Vinita; Gonnade, Rajesh G.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2024)
Herein, we disclose a simple one-pot method for an efficient regio- and stereoselective synthesis of 1,3,5-triaroylcyclohexanes from aryl vinyl ketones using potassium tert-butoxide. The developed protocol allows the construction of various symmetrically substituted cyclohexanes in good to excellent yields. The major product 2 also can be converted to the product 3 (all equatorial) conveniently by acid catalysis. This protocol features a good substrate scope and functional group compatibility.

Regulating the polyethylene microstructure by increasing steric crowding in naphthoxy imine-ligated Ni(II) complexes - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Polymer Chemistry, 2024)
Ligands play a prominent role in ethylene polymerization. However, it is a highly challenging task to regulate branching through ligand modifications. Here we report the synthesis of systematically sterically tailored naphthoxy imine-ligated nickel complexes (Ni1, Ni2, and Ni3), their performance in ethylene polymerization, and how the ligand steric controls branching in the resultant PE. Ni1-Ni3 were prepared in one step with an excellent yield (73-93%). The identity of these complexes was unambiguously ascertained using H-1, C-13, 2D NMR spectroscopy, mass analysis, and single-crystal X-ray diffraction. The molecular structure revealed a cis arrangement of alkyl/aryl and donor groups (C-Ni-D), which is necessary for initiating ethylene polymerization. Buried volume contours suggested Ni3 to be sterically the most bulky among the three. When exposed to ethylene, the three nickel complexes Ni1, Ni2, and Ni3 produced polyethylene with excellent activity. As predicted by buried volume calculations, dibenzhydryl-substituted Ni3 outperformed sterically less crowded Ni1 and Ni2. Careful analysis of the resultant PE disclosed that sterically less encumbered Ni1 and Ni2 produce PE with high branching (43-54 branches/1000-C atoms) density. However, the bulkiest Ni3 revealed much lower branching (28 branches/1000-C atoms) and a high TOF of 35 400 mol of PE per mol of Ni per h, along with a high molecular weight of PE (61 000 Da). The steric bulk in Ni3, most likely, reduces chain-walking and thus lowers branching in the resultant PE. As compared to the literature-reported analogous Pd1 catalyst, the Ni3 catalyst discloses high TOF, high molecular weight, and less branched, linear polyethylene.
Keywords: Catalyzed Olefin Polymerization; High-Temperature; Molecular Weight

Synthesis of imine-phenoxy ligated palladium complexes for norbornene homopolymerization - Birajdar, Rajkumar S.; Gupta, Poonam; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2024)
Metal complexes with tunable ligands play a crucial role in olefin polymerization and impart control over molecular weight, crystallinity, and stereoregularity. We report the single-step synthesis of imine-phenoxy ligands in excellent yields (81-93%). The identity of electronically tuned imine-phenoxy ligands was unambiguously ascertained by using a combination of spectroscopic and analytical methods. These ligands were treated with [Pd(COD)MeCl] in the presence of 2,6-lutidine, resulting in the formation of discrete mononuclear palladium complexes Pd1-Pd4 in excellent yields. 1-2D NMR spectroscopy, mass spectrometry analysis, and single-crystal X-ray diffraction confirmed the identity of the palladium complexes. X-ray analysis revealed a distorted square planar geometry around the palladium center. Proton NMR analysis suggested that the Pd1 catalyst was deshielded, indicating electronically deficient palladium metal compared to the other complexes. Moreover, the Pd1 catalyst showed the highest buried volume percentage (%Vbur = 44.9). When exposed to norbornene, Pd1-Pd4 were found to be active and produced poly(norbornene) (PNB). High-temperature SEC analysis revealed that the electronically deficient and sterically hindered Pd1 catalyst produced the highest molecular weight polymer (PNB 37.4 kDa). Boron and aluminum-based cocatalysts were screened, and MMAO was found to outperform others with high catalytic activity (up to 63.2 x 105 g of PNB (mol Pd)-1 h-1).

Thermally stable P-chiral supramolecular phosphines, their self-assembly and implication in Rh-catalyzed asymmetric hydrogenation - Chandanshive, Amol C.; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry-A European Journal, 2024)
P-chiral supramolecular phosphine ligands are crucial for asymmetric transformations, but their synthesis is tedious. We report a one-step synthesis of thermally stable P-chiral supramolecular phosphines and their performance in the asymmetric hydrogenation of functionalized alkenes. A rational designing and synthesis of (R, R)-QuinoxP* ligated palladium complex (Pd-2) in excellent yield is reported. This Pd-2 catalyzed a direct P-C coupling of 2,3-dihydro-1-H-phosphindole (A1)/1,2,3,4-tetrahydrophosphindoline (A2) with 1-(3-iodophenyl)urea (B1)/2-iodo /6-hydroxy pyridine (B2) and,produced corresponding ligands L1-L3. The P-C coupling between A1 and B2 produced 6-(2,3-dihydro-1H-phosphindol-1-yl)pyridine-2(1H)-one (L2) with an excellent enantiomeric excess of up to 99 %. L2 was found to be remarkably stable even at 150 degrees C and did not oxidize/hydrolyze for at least 24 hours in open air. Such thermal stability and an impediment to oxidation are unprecedented. L2 self-assembled and produced L2-C1 (Pt), L2-C2(Pd), and L2-C3(Rh) assemblies. The utility of the self-assembled P-chiral ligand was demonstrated in the Rh-catalyzed asymmetric hydrogenation (AH) of functionalized olefins. The L2-C3 catalyzed AH of functionalized alkenes and delivered chiral products with excellent enantioselectivity of >99 %. A small library of 16 substrates was subjected to AH using L2-C3 to produce chiral compounds with excellent conversion and ee.
Keywords: asymmetric hydrogenation; Asymmetric phosphination; P-chiral phosphine; Self-assembly; Supramolecular phosphine

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Uncovering diverse reactivity of NHCs withdiazoalkane: C-H activation, C=C bond formation,and access to N-heterocyclic methylenehydrazine - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Science, 2024)
N-heterocyclic carbenes (NHCs) have attracted significant attention due to their strong sigma-donating capabilities, as well as their transition-metal-like reactivity towards small molecules. However, their interaction with diazoalkanes remains understudied. In this manuscript, we explore the reactivity of a series of stable carbenes, encompassing a wide range of electronic properties, with Me3SiCHN2. 5-SIPr activates the C-H bond of Me3SiCHN2, resulting in the formation of a novel diazo derivative (1), while carbenes such as 5-IPr, 6-SIPr, and diamido carbene yield N-heterocyclic methylenehydrazine derivatives (3, 4, and 8). The reaction of Me3SiCHN2 with 5-ItBu unexpectedly leads to the formation of a triazole ring linked with the imidazole moiety via a CC double bond (6) alongside the azine product (7). Substituting the diazoalkane with diazoester consistently yields azine derivatives (9-12 and 14). Only in the case of 5-ItBu, an imidazolium salt with tetrazenide anion (13) was obtained as a side product. The reaction of 4 with HCl resulted in the desilylprotonation to form a salt, 5a, which undergoes deprotonation upon using bases such as Et3N and KHMDS to form N-heterocyclic methylene hydrazine, 5. Theoretical calculations have been conducted to elucidate the diverse mechanisms underlying product formation.

Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.

Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.

Cocrystals of the highly potent sickle cell anemia drug voxelotor with trimesic acid: a substantial enhancement in in vitro dissolution performance at physiological pH - Khan, Akram A.; Shaikh, Tabrez R.; George, Christy P.; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Global Blood Therapeutic's (GBT's) Voxelotor is an investigational oral therapy for treating sickle cell anemia. It functions by increasing the affinity between hemoglobin and oxygen, thereby preventing the sickling of red blood cells and altering the disease's pathology. The US FDA has approved Voxelotor for the treatment of sickle cell anemia and granted it an orphan drug status. However, Voxelotor is classified as a BCS class II, indicating poor water solubility. The current study explores the enhancement of Voxelotor's water solubility by forming cocrystals with trimesic acid (TMA). Novel cocrystals, cocrystal solvates, and hydrates of Voxelotor (Vox) with trimesic acid (TMA) have been developed to improve their solubility. The new solids were characterized using PXRD, DSC, TGA, XPS, HSM, and single-crystal X-ray diffraction studies, and the intermolecular interactions were quantified using Hirshfeld surface analysis. Detailed crystallographic analysis revealed strong O-H center dot center dot center dot N hydrogen bonding interactions between Vox and TMA, primarily involving the COOH functional group of TMA and the pyridine or pyrazole groups of Vox. Additionally, TMA molecules participate in further hydrogen bonding-either with themselves or with solvates, including hydrates, through mono- or dimeric O-H center dot center dot center dot O H-bonding synthons. In vitro solubility studies demonstrated a significant increase in the solubility of Voxelotor in the Vox-TMA cocrystals compared to the pristine drug at physicochemical pH 4.5 and 6.8. Stability studies confirmed that the nonsolvated multicomponent crystal retains their structural integrity under nonambient conditions without undergoing polymorphic phase transitions. In contrast, the solvated crystals, including hydrates, undergo phase transitions within the temperature range of 100-130 degrees C, losing solvents and converting into one of the nonsolvated cocrystal forms. These findings suggest that the novel Vox-TMA cocrystals have the potential to enhance the therapeutic performance and clinical utility of Voxelotor.

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation

Quality by design-based development and validation of a stability-indicating RP-HPLC method for quantitative estimation of enzalutamide in eutectic mixtures - Wannur, Vishal Irappa; Patil, Archana S.; Sawadi, Bhavana; Koli, Rahul; Shaligram, Parth Shailendra; shet, Nagabhushan; Gonnade, Rajesh G. (SSC Plus, 2025)
Metastatic castration-resistant prostate cancer presents a significant clinical challenge, with Enzalutamide—an androgen receptor inhibitor—serving as a standard therapeutic agent. Despite its efficacy, poor aqueous solubility (Biopharmaceutics classification system Class II) limits its bioavailability, necessitating advanced formulation strategies. This study reports a robust and validated Reverse Phase High Performance Liquid Chromatography (RP-HPLC) method for quantifying enzalutamide in bulk and eutectic formulations. A Quality by Design framework employing a Box–Behnken design was used to optimize chromatographic parameters: 60% acetonitrile, 1 mL/min flow rate, 30°C column temperature, and 234 nm detection wavelength. The method exhibited strong linearity (2–12 µg/mL, r2 = 0.9985) with a limit of detection and limit of quantification of 0.464 and 1.40 µg/mL, respectively. Validation per International Council for Harmonisation Q2 (R1/R2) confirmed accuracy, precision, robustness, and system suitability. Forced degradation studies verified its stability-indicating capability. Eutectic mixtures with succinic acid, caffeine, and ferulic acid were prepared via liquid-assisted grinding and characterized using powder x-ray diffraction, confirming crystalline eutectic formation. Recovery ranged from 96.7% to 99.8%, supporting the method's applicability in routine analysis and formulation development. Greenness evaluation using various tools confirmed the method's low environmental impact and high operational feasibility. This validated RP-HPLC method enables reliable quantification of enzalutamide, supporting the development of novel bioavailability-enhancing formulations for effective prostate cancer management.

Separation of isomers of chiral thiourea derivatives via spontaneous resolution and rationale of molecular recognition - Dwivedi, Astha M.; Gonnade, Rajesh G.; Sahoo, Suban K.; Bedekar, Ashutosh V. (CrystEngComm, 2025)
Enrichment of enantiomers during crystallization of racemic thiourea derivatives was investigated. The spontaneous resolution of a chiral thiourea derivative via preferential crystallization is attributed to thermodynamic stability when molecules of identical chirality bind with each other in the crystal lattice. Single crystal X-ray analysis reveals the interactions responsible for self-recognition of molecules of the same chirality in the unit cell. The tendency of the thiourea derivative to form a conglomerate is supported by IR spectroscopy, thermal analysis and computational studies.

Sila[1]ferrocenophanes with Bulky Substituents - Ajithkumar, V. S.; Bisai, Milan Kumar; Yuvaraj, K.; Gonnade, Rajesh G.; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
In this study, sila[1]ferrocenophanes with sterically bulky groups such as tris(trimethylsilyl) or N-heterocyclic iminato located at the bridging silicon atom are synthesized. The reactions of silicon-bound chloride in Fe(eta 5-C5H4)2SiCl2 (1) with K[Si(SiMe3)3] and silylated N-heterocyclic imine result in sila[1]ferrocenophanes 2 and 3 with bulky silicon- and nitrogen-based substituents at the ansa-bridge via elimination of KCl and Me3SiCl. Subsequently, the reduction of 1 is attempted using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (popularly known as Mashima reagent), which leads to the elimination of Me3SiCl and generation of 1,4-dihydropyrazine-spanned sila[1]ferrocenophanes (4). All the compounds are structurally characterized.
Keywords: ansa-bridges; ferrocenophanes; hypersilyls; Mashima reagents; N-heterocyclic imines

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Synthesis, crystal structure and Hirshfeld surface analysis of 5-methyl-2-[(1,3-thiazol-2-yl)sulfanyl]-1,3,4-thiadiazole - Kinshakova, Ekaterina; Torambetov, Batirbay; Bharty, Manoj K.; Atashov, Aziz; Rasulov, Abdusamat; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Acta Crystallographica Section E Crystallographic Communications, 2025)
The title compound, C<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">6H<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">5N<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3S<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">3, consists of two biologically relevant heterocyclic units, suggesting potential biological activity and possible use as a ligand in metal complexation. The compound crystallizes in the monoclinic space group P2<span style="color-scheme: revert; forced-color-adjust: revert; mask: revert; math-depth: revert; position: revert; position-anchor: revert; text-size-adjust: revert; appearance: revert; color: rgb(27, 27, 27); font-family: Cambria, "Cambria Math", Charter, "Times New Roman", Times, stixgeneral, serif; font-feature-settings: revert; font-kerning: revert; font-language-override: revert; font-optical-sizing: revert; font-palette: revert; font-size: revert; font-size-adjust: revert; font-stretch: revert; font-synthesis: revert; font-variant-alternates: revert; font-variant-east-asian: revert; font-variant-emoji: revert; font-variant-numeric: revert; font-variant-position: revert; font-variation-settings: revert; position-area: revert; text-orientation: revert; text-rendering: revert; text-spacing-trim: revert; -webkit-font-smoothing: revert; -webkit-locale: revert; -webkit-text-orientation: revert; -webkit-writing-mode: revert; writing-mode: revert; zoom: revert; accent-color: revert; place-content: revert; place-items: revert; place-self: revert; alignment-baseline: revert; anchor-name: revert; anchor-scope: revert; animation-composition: revert; animation: revert; app-region: revert; aspect-ratio: revert; backdrop-filter: revert; backface-visibility: revert; background-attachment: revert; background-blend-mode: revert; background-clip: revert; background-image: revert; background-origin: revert; background-position: revert; background-repeat: revert; background-size: revert; baseline-shift: revert; baseline-source: revert; block-size: revert; border-block: revert; border: revert; border-radius: revert; border-collapse: revert; border-end-end-radius: revert; border-end-start-radius: revert; border-inline: revert; border-start-end-radius: revert; border-start-start-radius: revert; inset: revert; box-decoration-break: revert; box-shadow: revert; box-sizing: revert; break-after: revert; break-before: revert; break-inside: revert; buffered-rendering: revert; caption-side: revert; caret-animation: revert; caret-color: revert; caret-shape: revert; clear: revert; clip: revert; clip-path: revert; clip-rule: revert; color-interpolation: revert; color-interpolation-filters: revert; color-rendering: revert; columns: revert; column-fill: revert; gap: revert; column-rule: revert; column-span: revert; contain: revert; contain-intrinsic-block-size: revert; contain-intrinsic-size: revert; contain-intrinsic-inline-size: revert; container: revert; content: revert; content-visibility: revert; corner-shape: revert; corner-block-end-shape: revert; corner-block-start-shape: revert; counter-increment: revert; counter-reset: revert; counter-set: revert; cursor: revert; cx: revert; cy: revert; d: revert; display: revert; dominant-baseline: revert; dynamic-range-limit: revert; empty-cells: revert; field-sizing: revert; fill: revert; fill-opacity: revert; fill-rule: revert; filter: revert; flex: revert; flex-flow: revert; float: revert; flood-color: revert; flood-opacity: revert; grid: revert; grid-area: revert; height: revert; hyphenate-character: revert; hyphenate-limit-chars: revert; hyphens: revert; image-orientation: revert; image-rendering: revert; initial-letter: revert; inline-size: revert; inset-block: revert; inset-inline: revert; interactivity: revert; interest-delay: revert; interpolate-size: revert; isolation: revert; lighting-color: revert; line-break: revert; line-height: revert; list-style: revert; margin-block: revert; margin: revert; margin-inline: revert; marker: revert; mask-type: revert; math-shift: revert; math-style: revert; max-block-size: revert; max-height: revert; max-inline-size: revert; max-width: revert; min-block-size: revert; min-height: revert; min-inline-size: revert; min-width: revert; mix-blend-mode: revert; object-fit: revert; object-position: revert; object-view-box: revert; offset: revert; opacity: revert; order: revert; outline: revert; outline-offset: revert; overflow-anchor: revert; overflow-block: revert; overflow-clip-margin: revert; overflow-inline: revert; overflow-wrap: revert; overflow: revert; overlay: revert; overscroll-behavior-block: revert; overscroll-behavior-inline: revert; overscroll-behavior: revert; padding-block: revert; padding: revert; padding-inline: revert; page: revert; page-orientation: revert; paint-order: revert; perspective: revert; perspective-origin: revert; pointer-events: revert; position-try: revert; position-visibility: revert; print-color-adjust: revert; quotes: revert; r: revert; reading-flow: revert; reading-order: revert; resize: revert; rotate: revert; ruby-align: revert; ruby-position: revert; rx: revert; ry: revert; scale: revert; scroll-behavior: revert; scroll-initial-target: revert; scroll-margin-block: revert; scroll-margin: revert; scroll-margin-inline: revert; scroll-marker-group: revert; scroll-padding-block: revert; scroll-padding: revert; scroll-padding-inline: revert; scroll-snap-align: revert; scroll-snap-stop: revert; scroll-snap-type: revert; scroll-target-group: revert; scroll-timeline: revert; scrollbar-color: revert; scrollbar-gutter: revert; scrollbar-width: revert; shape-image-threshold: revert; shape-margin: revert; shape-outside: revert; shape-rendering: revert; size: revert; speak: revert; stop-color: revert; stop-opacity: revert; stroke: revert; stroke-dasharray: revert; stroke-dashoffset: revert; stroke-linecap: revert; stroke-linejoin: revert; stroke-miterlimit: revert; stroke-opacity: revert; stroke-width: revert; tab-size: revert; table-layout: revert; text-align-last: revert; text-anchor: revert; text-autospace: revert; text-box: revert; text-combine-upright: revert; text-decoration-line: revert; text-decoration-skip-ink: revert; text-emphasis: revert; text-emphasis-position: revert; text-justify: revert; text-overflow: revert; text-shadow: revert; text-underline-offset: revert; text-underline-position: revert; text-wrap-style: revert; timeline-scope: revert; touch-action: revert; transform: revert; transform-box: revert; transform-origin: revert; transform-style: revert; transition: revert; translate: revert; user-select: revert; vector-effect: revert; vertical-align: revert; view-timeline: revert; view-transition-class: revert; view-transition-group: revert; view-transition-name: revert; visibility: revert; border-spacing: revert; -webkit-box-align: revert; -webkit-box-decoration-break: revert; -webkit-box-direction: revert; -webkit-box-flex: revert; -webkit-box-ordinal-group: revert; -webkit-box-orient: revert; -webkit-box-pack: revert; -webkit-box-reflect: revert; -webkit-line-break: revert; -webkit-line-clamp: revert; -webkit-mask-box-image: revert; -webkit-rtl-ordering: revert; -webkit-ruby-position: revert; -webkit-tap-highlight-color: revert; -webkit-text-combine: revert; -webkit-text-decorations-in-effect: revert; -webkit-text-fill-color: revert; -webkit-text-security: revert; -webkit-text-stroke-color: revert; -webkit-user-drag: revert; width: revert; will-change: revert; word-break: revert; x: revert; y: revert; z-index: revert;">1/c and features non-classical intermolecular C—H⋯N hydrogen bonds, along with π–π stacking interactions that contribute to the crystal cohesion. Hirshfeld surface analysis highlights significant intermolecular interactions including, among others, N⋯H/H⋯N, S⋯H/H⋯S, and S⋯C/C⋯S contacts.

Synthesis, crystal structure and Hirshfeld surface analysis of bis[2-amino-5-(ethylsulfanyl)-1,3,4-thiadiazol-3-ium] bis(perchlorato-κO)bis(picolinato-κ2N,O)copper(II) - Khojabaeva, Gulnaz; Torambetov, Batirbay; Gonnade, Rajesh G.; Uzakbergenova, Zamira; Rasulov, Abdusamat; Kadirova, Shakhnoza (Acta Crystallographica Section E, Crystallographic Communications, 2025)

Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc

Synthesis of diamido N-heterocyclic imines (DAC = NH) via staudinger or reductive N-N bond cleavage approach - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
This report communicates the first examples of N-heterocyclic imines based on electrophilic diamido carbenes (DACs). While 2 is prepared by classical Staudinger synthesis, 4 is obtained via an unusual reductive N-N bond cleavage of an azine by HCl. The exocyclic C=N bond lengths in 2 and 4 are substantially shorter than those based on N-heterocyclic carbenes and cyclic (alkyl)(amino)carbene reflecting the electrophilic character of DACs.

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.

Divergent synthesis of meyers' lactams and medium lactams via cyclocondensation of γ-ylidene-butanolides with chiral amino alcohols - Sadanande, Megha V.; Sharma, Paridhi; Gonnade, Rajesh G.; Kontham, Ravindar (Journal of Organic Chemistry, 2026)
A novel methodology for constructing Meyers' lactams (pyrrolidino-oxazolidines), related to biologically potent natural and synthetic scaffolds, has been developed via an unprecedented tandem cyclocondensation of chiral 2-amino alcohols and gamma-ylidene-butanolides. The process proceeds through the initial formation of an ene-lactam intermediate, followed by a Bro/nsted acid (PPTS)-catalyzed ring closure. Under stoichiometric amounts of a Lewis acid (TiCl4), the same set of building blocks affords medium lactams featuring eight-membered ring systems with an exo-enol ether segment. This divergent synthetic strategy enables the efficient generation of a library of Meyers' lactams and medium lactams with good yields and diastereoselectivity.

Exploring the interplay of electron density distribution and electrostatic potential in the interaction of nilutamide and flutamide with androgen receptors using quantum crystallography - Balasubramanian, Hemalatha; Poomani, Kumaradhas; Kandasamy, Saravanan; Hathwar, Venkatesha R.; Gonnade, Rajesh G. (RSC Advances, 2026)
Prostate cancer is a malignant disease commonly found in men. Androgens support the growth and survival of prostate cancer cells. To control this growth and the spread of cancer cells, anti-androgen drugs are necessary to block androgen activity. Effective blocking of androgens depends mainly on the structure, intermolecular interactions and charge density distribution, electrostatic potential (ESP) and binding affinity of drug molecules. Nilutamide (NIL) and flutamide (FLU) are two structurally related non-steroidal anti-androgen drugs (NSAAs) which exhibit serious side effects. The present study explores the charge density distribution, electrostatic potential and intermolecular interactions of NIL and FLU determined from a high-resolution X-ray diffraction experiment and a solid-state quantum chemical theoretical study. Topological analysis of charge density reveals the electron density at the bond critical points of chemical bonds and intermolecular interactions. The electrostatic potential derived from the charge density distribution of both molecules in the crystal has been mapped, which allows a prediction of how the electrostatic interactions, hydrogen bonds, and van der Waals forces govern the binding of these two drug molecules with the androgen receptor at the electronic level. The ESP of interacting groups of both molecules in the androgen active site is approximated to the ESP of those groups in the crystals. The charge density distribution and the electrostatic potential of both molecules were compared. The difference in charge density is reflected in the ESP of NO2, CF3 and NH groups and the aromatic ring of both molecules, which is important for drug binding, metabolic stability and toxicity. A molecular docking simulation of both molecules with androgen receptors shows the difference in interactions and binding affinity in the binding pocket of the androgen receptor. The results of the high-resolution X-ray experiment and the advanced computational charge density study of NIL and FLU allows us to understand drug binding and is useful to relate their differing biological effects and toxicities at the electronic level. This information pertains to the design of a new potential androgen inhibitor with improved binding affinity and fewer side effects.

Modular synthesis of triaroyl cyclopropanes via a formal cyclotrimerization of phenacyl bromides and their transformation into diazabicycles - Jadhav, Hrutik Madhavrao; Penta, Santhosh; Pannuri, Lavanya Lahari; Rangarao, Chilukuri; Gonnade, Rajesh G.; Manda, Rajesh (Organic Letters, 2026)
Step-efficient cyclotrimerization reactions are entrancing approaches for saturated carbocycles. In this context, we demonstrate the alpha-bromocarbonyl (1+1+1) cyclotrimerization modularity to obtain stereoselective trisubstituted cyclopropanes under metal-free conditions. These cyclopropanes were condensed with hydrazine to afford diazabicyclic adducts and further expanded through a ring expansion reaction. In contrast to the classical alkylating reactivity, alpha-bromocarbonyl cyclotrimerization was also achieved by using various nucleophiles. A wide range of bromoacyl substrates established the broad scope of the transformation.

NHC-based diazo compounds: pathways to N2 liberation or dimerization - Balayan, Kajal; Tiwari, Prabhakar; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Journal of Organic Chemistry, 2026)
We previously reported the C-H bond cleavage of Me3SiCHN2 by 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene (5-SIPr) to form 1. In this article, we showed that electron-poor diamido carbene 5-tBuDAC also cleaves the C-H bond of Me3SiCHN2 to form 5, unlike its ring-expanded congener 6-DippDAC, which forms N-heterocyclic methylene hydrazine. The divergence of reactivity has been explained with the help of DFT studies. Further divergence occurs when 1 and 5 were reacted with HCl. While dimerization was observed with 5-SIPr based diazoalkane to give quinoidal tetrazine (2), N2 elimination occurs from 5-tBuDAC based diazoalkane to afford 7 and 8. This contrasting behavior highlights the subtle yet profound influence of the N-heterocyclic carbene (NHC) framework on the fate of the diazo units. DFT studies shed light about the mechanism for the formation of 2 as well as reveal that N2 elimination is thermodynamically favored over dimerization for 5.

Novel cocrystal of quercetagetin: in vitro and in vivo insights into biopharmaceutical performance - Suryawanshi, Smita; Shaligram, Parth; Gonnade, Rajesh G.; Patil, Sharvil (Pharmaceutical Research, 2026)
Purpose Quercetagetin (QTGN) is a naturally occurring flavonol predominantly sourced from marigold flowers and possesses notable therapeutic potential, including antidiabetic, anticancer, antioxidant, anti-inflammatory, and antiviral properties. However, poor aqueous solubility and in turn bioavailability restrict therapeutic utility of QTGN. Crystal engineering is one of the approaches proven to be fruitful in resolving the solubility issues of many active pharmaceutical ingredients (APIs). Method In the present work, a cocrystal of QTGN using betaine (BET) as coformer viz. Quercetagetin & sdot;betaine & sdot;ethanol (QTGN & sdot;BET & sdot;EtOH) was synthesized using the solvent evaporation method. It was further characterized using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric analysis (TGA), Powder X-ray diffraction (PXRD), and single crystal XRD (SCXRD). Result FTIR studies confirmed hydrogen bonding between QTGN and BET. PXRD studies showed formation of new crystalline phase. The prepared cocrystal had stoichiometric ratio of 1:1:1 between QTGN, BET, and ethanol forming cocrystal ethanolate and shared robust hydroxyl & ctdot;carboxylate supramolecular synthon as confirmed by TGA and SCXRD, respectively. Equilibrium solubility study and in vitro dissolution study showed a significant improvement (p < 0.0001) in aqueous solubility of QTGN upon its cocrystallization with BET. Furthermore, in vivo pharmacokinetic study revealed a 1.28-fold increase in bioavailability of QTGN when formulated as cocrystal solvate. The prepared cocrystal was found to be stable over a period of six months at 40 degrees C and 75% RH when analyzed using PXRD studies. Conclusion The current work represents a frontier in pharmaceutical formulation, providing a means to fully harness the therapeutic potential of QTGN using cocrystal approach.
Keywords: betaine; Bioavailability; cocrystal; quercetagetin; USP apparatus IV

Reactions of saturated NHC·boranes with electron-deficient alkynes and alkenes. borirane formation, their reactivities, and coupling of tetracyanoethylene - Amrutha, P. R.; Kundu, Gargi; Ganesh, Vemuri Lakshmi; Gonnade, Rajesh G.; Gopakumar, Gopinadhanpillai; Sen, Sakya S. (Dalton Transactions, 2026)
In this study, we describe the reactions of five- and six-membered saturated N-heterocyclic carbene boranes (NHC & centerdot;BH3) with electron-deficient alkenes and alkynes. Notably, both five- and six-membered saturated NHCs form boriranes upon the reaction of NHC & centerdot;BH3 with dimethyl acetylene dicarboxylate (DMAD). However, their reactivity with HCl differs: the five-membered saturated NHC-stabilized borirane undergoes ring opening in toluene/THF, whereas the six-membered saturated NHC-stabilized borirane undergoes ring expansion, forming exclusively a boralactone irrespective of solvent. Interestingly, when acetonitrile is used as a solvent, the five-membered saturated NHC-stabilized borirane yields both ring-opening and ring-expansion products. To remove the hydrogen attached to the boron atom in boriranes, we reacted the five-membered saturated NHC-stabilized borirane with AlCl3 and B(C6F5)(3), resulting in azaborolium cation or adduct formation, respectively. Transitioning from an electron-deficient alkyne to an alkene, the reaction of six-membered saturated NHC & centerdot;BH3 with tetracyanoethylene (TCNE) led to the unusual coupling of two TCNE molecules.

Smallest acyclic tricationic molecule containing a Bis(phosphine)-stabilized low-valent triantimony-based Unit - Mukherjee, Nilanjana; Peerless, Benjamin; Nadurata, Vincent L.; Kumar, Vikas; Sangole, Mayur P.; Singh, Kirandeep; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Kruk, Robert; Weigend, Florian; Dehnen, Stefanie; Gonnade, Rajesh G.; et al. (Nature Communications, 2026)
Element-element bonded multiply charged cationic species are well known as dimers or small cyclic oligomers in the condensed phase. However, the smallest acyclic version, a trinuclear unit possessing greater than a monocationic charge, has remained elusive. Here we introduce a bis(phosphine) supported low valent triantimony-based tricationic compound as a new entrant in this field. Structural elucidation and electronic understanding reveal a W-shaped tricationic unit comprising of a three-center four-electron sigma-bonded triantimony moiety that is terminally capped by bis(phosphine) ligands, with the central antimony atom having two lone pairs of electrons. The unique counter trianion [Sb(O)2(OTf)4]3- (OTf = CF3SO3) possesses reactive polar Sb delta+-O delta- bonds, the structure of which is determined from single crystal X-ray diffraction analysis. The ensemble of reactive molecular fragments found in this highly charged antimony-based compound makes it thermally unstable. Nonetheless, this fully characterized fleeting species shows a diverse reactivity profile, advancing the isolation of various novel antimony compounds, including the formation of a distinct low-valent antimony-cobalt carbonyl cluster.

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.

Transition metal complexes of Thiadiazole-Picolinic acid: Crystal structures, DFT insights and anticancer activity - Torambetov, Batirbay; Khojabaeva, Gulnaz; Bharty, M. K.; Gupta, Sushil K.; Kadirova, Shakhnoza; Pradeep, S.; Dastager, Syed G.; Gonnade, Rajesh G. (Journal of Molecular Structure, 2026)
Five novel transition metal complexes [Ni(H2aeth)2(Pic)2] (1), [Co(H2aeth)2(Pic)2] (2), [Ni(H2aeth)2(Pic)(HPic)] ClO4 (3), [Co(H2aeth)2(Pic)(HPic)]ClO4 (4) and [Zn(H2aeth)2 (Pic)(HPic)]ClO4 (5) were synthesized using a 2amino-5-ethylthio-1,3,4-thiadiazole (H2aeth) and picolinic acid (HPic) as co-ligands. These complexes were characterized by FT-IR, UV-Vis., X-ray photoelectron spectroscopy, TG-DTA, and single-crystal X-ray techniques. Crystallographic analysis confirmed distorted octahedral geometries around the metal centers with extensive hydrogen bonding networks promoting supramolecular assembly in the solid state. X-ray photoelectron spectroscopy (XPS), validated the +2 oxidation state of each metal center. Thermal studies indicated multistep decomposition processes resulting in the formation of metal oxides. Density functional theory (DFT) and timedependent DFT calculations were employed to explore electronic structures and predict UV-Vis. transitions, which showed good agreement with experimental data. Frontier molecular orbital (FMO) analysis revealed that Ni(II) complexes 1 and 3 are softer and more reactive, consistent with their observed biological activity. The anticancer potential of complexes 1-5 was evaluated in vitro using the MCF-7 human breast cancer cell line and the MTT assay. Complex 1 exhibited the strongest cytotoxicity (IC50 = 26.5 mu g/mL) followed by complexes 3 (34.9 mu g/mL), 4 (46.4 mu g/mL), 2 (81.1 mu g/mL), and 5 (103.3 mu g/mL). The observed activity trends correlate with metal identity and coordination environment, underlining the role of electronic and structural factors in modulating bioactivity. These findings suggest that thiadiazole-picolinate metal complexes, particularly those based on Ni (II), are promising scaffolds for anticancer drug development.
Keywords: Anti-cancer activity; crystal structure; DFT calculation; MCF-7 cell line; Picolinic acid; Thiadiazole complexes

Unveiling the reactivity of N-heterocyclic methylene hydrazines - Balayan, Kajal; Biswas, Arindam; Sharma, Himanshu; Tiwari, Prabhakar; Vanka, Kumar; Gonnade, Rajesh G.; Rath, Arup K.; Sen, Sakya S. (Dalton Transactions, 2026)
We present the first reactivity profile of N-heterocyclic methylene hydrazines, revealing distinct competition between steric and electronic control. Reactions with HCl are electronically driven, resulting in protonation at the proximal nitrogen, while the bulky Lewis acid B(C6F5)3 coordinates to the sterically accessible distal nitrogen. Additionally, we demonstrate that these scaffolds undergo spontaneous, base-free HCN elimination with tetracyanoethylene (TCNE) to form highly conjugated molecules with significantly reduced HOMO-LUMO gaps.